Adhesive tape

By adjusting the characteristics of the base layer and the adhesive layer of the adhesive tape, the specific cracking adhesive relationship is met, and the problem of cracking or residual adhesive during the re-leaving process is solved, thereby achieving excellent re-leaching properties of the adhesive tape.

CN119799196APending Publication Date: 2025-04-11DIC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411964546.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-01-21
Filing Date
2021-01-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing adhesive tape is prone to cracking or residual adhesive during the re-peeling process, resulting in the problem that it cannot be peeled off.

Method used

By adjusting the characteristics of the base material layer and the adhesive layer of the adhesive tape, the breaking stress of the base material layer is between 1 and 100 MPa, the breaking elongation is between 400 and 3000%, and the specific split adhesive force relationship (P400/P0≤0.9) is met to improve the releasability of the adhesive tape.

Benefits of technology

Excellent releasability of the adhesive tape in partially stripped state is achieved, reducing the force and risk of fracture during the stripping process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218024440000031
    Figure BDA0005218024440000031
  • Figure BDA0005218024440000121
    Figure BDA0005218024440000121
  • Figure BDA0005218024440000211
    Figure BDA0005218024440000211
Patent Text Reader

Abstract

The purpose of the present invention is to provide an adhesive tape having excellent removability in a state in which a portion of the adhesive tape has been peeled off from an adherend. The present invention is an adhesive tape provided with a base material layer and an adhesive layer, the base material layer having a breaking stress of 1-90 MPa and an elongation at break of 400-3000%, and satisfying the following relational expression (i): [number 1] P400 / P0 < = 0.9 (i) (in the relational expression (i), P0 represents an initial adhesive force (N / 25 mm) of the adhesive tape, and P400 represents an adhesive force (N / 25 mm) when the adhesive tape is stretched by 400%. ).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the Chinese invention patent application with application number: 202180009038.3, application date: January 14, 2021, and invention name: “Adhesive Tape”. Technical Field

[0002] The present invention relates to an adhesive tape. Background Art

[0003] Adhesive tapes have excellent workability and high bonding reliability. Therefore, adhesive tapes are widely used as a bonding means to fix components of relatively large electronic devices such as thin-film televisions, home appliances, and office automation equipment, or to fix components of relatively small electronic devices such as portable electronic terminals, cameras, and personal computers. More specifically, in various industrial fields such as office automation equipment, IT and home appliances, and automobiles, adhesive tapes are not only used for fixing metal plates constituting large electronic devices or fixing exterior components to housings, fixing exterior components or rigid components such as batteries to small electronic devices, and temporarily fixing the components, but are also used for labeling purposes such as displaying product information. In recent years, from the perspective of protecting the global environment and for the purpose of saving resources, there is an increasing trend in the above-mentioned industrial fields to reuse or re-use the reusable or reusable parts used in the products by disassembling the products after use. At this time, when using an adhesive tape, it is necessary to peel off the adhesive tape attached to the parts, but the adhesive tape generally has a strong adhesive force and is attached to multiple parts of the product, so the operation of peeling them off requires a considerable amount of labor. Therefore, an adhesive tape that can be relatively easily peeled off and removed when reused or re-used is needed.

[0004] As a technology related to an adhesive tape that can be easily peeled and removed, for example, Patent Document 1 can be cited. Patent Document 1 discloses an adhesive tape, which has an adhesive portion and a handle portion, and can be peeled off from the adherends on both sides of the adhesive portion by clamping the handle portion and stretching the adhesive tape in a direction roughly parallel to the adhesive surface. However, in small electronic devices, since the space between the components in the electronic device is narrow, there is a problem that it is difficult to stretch and peel the adhesive tape attached to the space in a direction parallel to the adhesive surface. As a technology to solve this problem, Patent Document 2 discloses an adhesive tape that can be removed again by stretching it in a direction of 30° relative to the adhesive surface. Prior art literature Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-124289 Patent Document 2: Japanese Patent Application Publication No. 2016-26255 Summary of the invention Technical Problems to be Solved by the Invention

[0006] In the technology of the above-mentioned patent document 1, after the adhesive tape was aged in an oven at 40°C for 30 minutes, the holding force of the adhesive tape with a 1kg weight hanging thereon was evaluated, but the re-peelability itself was not studied. On the other hand, the technology of the above-mentioned patent document 2 studied how to stretch and remove the adhesive article without damage and without residual adhesive residue. However, the above-mentioned patent document 2 did not study the re-peelability in a state where a part of the adhesive tape was peeled off from the adherend. Usually, when the adhesive tape is stretched from the adherend and peeled off in a direction of 90°, the adhesive tape is peeled off while contacting the adherend. Therefore, if the peeling is temporarily stopped in the process of peeling off, in the case of the previous adhesive tape, the temporarily peeled adhesive tape will be re-adhered to the adherend. As a result, the problem of the adhesive tape breaking or the adhesive layer remaining during peeling off occurs, and thus the problem of being unable to peel off again occurs. Therefore, an object of the present invention is to provide a pressure-sensitive adhesive tape (for example, a pressure-sensitive adhesive tape) having excellent removability in a state where a portion of the pressure-sensitive adhesive tape has been peeled off from an adherend. Solutions to technical problems

[0007] The present inventors have conducted intensive studies in view of the above problems and have found that the above problems can be solved by establishing a specific relationship between the initial cleavage adhesive force of the adhesive tape and the cleavage adhesive force when the adhesive tape is stretched by a predetermined ratio and satisfying this relationship, thereby completing the present invention.

[0008] That is, the present invention is as follows. [1] The present invention is a pressure-sensitive adhesive tape comprising a substrate layer and a pressure-sensitive adhesive layer (eg, a pressure-sensitive adhesive layer). The substrate layer has a breaking stress of 1 to 100 MPa and a breaking elongation of 400 to 3000%. The adhesive tape satisfies the following relationship (i): [Number 1] P 400 / P0≤0.9 (i) (In the above relational formula (i), P0 represents the initial cleavage adhesive force (N / cm 2 ), P 400 The cleavage adhesive strength (N / cm2) when the adhesive tape is stretched 400% 2 ). ).

[0009] [2] In the present invention, the storage modulus G' (23°C) of the adhesive layer is preferably 1.0×10 5 ~1.0×10 7 Pa. [3] In the present invention, the adhesive layer preferably contains a filler. [4] In the present invention, it is preferred that the adhesive layer contains a styrene-based block copolymer. [5] In the present invention, it is preferred that the adhesive layer comprises a triblock copolymer having a repeating unit represented by the general formula (1): [Chemistry 1] (In the above general formula (1), A, B and C each independently represent a repeating unit, A and C each independently represent an alkyl methacrylate monomer unit, B represents an alkyl acrylate monomer unit, p, q and r each independently represent the degree of polymerization of each monomer unit, A and C may be the same, or may be alkyl methacrylate monomer units having different chemical structures. In the above general formula (1), * represents the bonding position with other atoms. ). [6] In the present invention, it is preferred that the filler is a silicone resin. [7] In the present invention, it is preferred that the adhesive layer further contains a tackifier resin (for example, a pressure-sensitive adhesiveness-imparting resin). Effects of the Invention

[0010] The present invention can provide a pressure-sensitive adhesive tape having excellent removability from a state where a portion of the pressure-sensitive adhesive tape has been peeled off from an adherend. DETAILED DESCRIPTION

[0011] Hereinafter, an embodiment of the present invention (hereinafter referred to as “the present embodiment”) will be described in detail, but the present invention is not limited to the present embodiment.

[0012] (Adhesive tape) The adhesive tape of this embodiment is an adhesive tape having a substrate layer and an adhesive layer. In addition, the fracture stress of the substrate layer is 1 to 100 MPa. In addition, the adhesive tape of this embodiment satisfies the following relational expression (i): [Number 2] P 400 / P0≤0.9 (i) (In the above relational formula (i), P0 represents the initial cleavage adhesive strength of the adhesive tape (N / cm 2 ), P 400 The cleavage adhesive strength (N / cm2) when the adhesive tape is stretched 400% 2 ). ).

[0013] The pressure-sensitive adhesive tape of the present embodiment has such a configuration, and can achieve excellent re-peelability in a state where a portion of the pressure-sensitive adhesive tape has been peeled off from an adherend.

[0014] Specifically, the base layer of the adhesive tape of the present embodiment has a breaking stress of 1 to 100 MPa and a breaking elongation of 400 to 3000%. In the initial stage of peeling the adhesive tape from the adherend (initial elongation of the adhesive tape), the operator can stretch it with a lighter force. In addition, even if the operator stretches it at a faster speed through the peeling operation, the adhesive tape can be peeled off from the adherend without breaking (and can be peeled off again).

[0015] Furthermore, since the pressure-sensitive adhesive tape of the present embodiment satisfies the above-mentioned relational expression (i), it is possible to achieve excellent removability in a state where a portion of the pressure-sensitive adhesive tape has been peeled off from an adherend.

[0016] The initial cleavage adhesive force P0 (N / cm2) of the adhesive tape in the above relational expression (i) is 2 ) refers to the strength of the adhesive tape when it is attached to the adherend in a normal state and then stretched under specified conditions to peel off the adherend. In this specification, the initial cleavage adhesion P0 (N / cm 2 ). As the test piece, for the convenience of evaluation, an adhesive tape having an adhesive layer and a release liner on both sides of the substrate layer was used. More specifically, the adhesive tape was cut into a size of 30 mm × 50 mm and used as a test piece. The release liner on one side of the test piece was peeled off and attached to the surface of a 3 mm thick stainless steel (SUS) plate. The release liner on the other side was peeled off and attached to the surface of a 10 mm square of a 10 mm × 10 mm × 40 mm long test piece. The test piece was subjected to a 50 N / cm 2 Then, immediately after the above-mentioned patch is attached in an atmosphere of 23°C and 50%RH, the stainless steel sheet constituting the above-mentioned test piece of the above-mentioned patch is stretched at a speed of 1000 mm / min in an atmosphere of 23°C and 50%RH, and the strength of peeling the stainless steel sheet is defined as the initial cleavage adhesive force P0.

[0017] In the present invention, the initial cleavage adhesive force P0 (N / cm 2 ) is preferably 0.1 to 200 N / cm 2 , more preferably 1 to 150 N / cm 2 , more preferably 50 to 130 N / cm 2 . If the above-mentioned splitting adhesive force P0 is 0.1 to 200 N / cm 2 , it is easy to take into account both adhesion and disassembly.

[0018] The adhesive force P at 400% stretch in the above relational formula (i) is 400 (N / cm 2 ) refers to the strength of the adhesive tape when it is attached to the adherend in a state of being stretched to 400% of its length and then peeled off the adherend under the specified conditions. In this specification, the adhesive strength P when stretched to 400% is calculated by the following evaluation conditions and evaluation methods. 400 (N / cm 2 ). As a test piece, for the convenience of evaluation, an adhesive tape having an adhesive layer and a release liner on both sides of the substrate layer was used. More specifically, the adhesive tape was cut into a size of 30 mm × 50 mm and used as a test piece. The release liners on both sides of the test piece were peeled off, and handles were made at both ends of the test piece. A strong adhesive double-sided tape for fixing the stretched tape was attached to the surface of a 2 mm thick stainless steel plate. The test piece was stretched to 400% of its length. After the double-sided adhesive tape was attached to the surface of the stainless steel plate, a 10 mm square surface of a 10 mm × 10 mm × 40 mm long test piece was attached to the surface of the other side, and then the test piece was subjected to a 50 N / cm 2 The adhesive was pressed for 10 seconds to obtain a patch. Then, the stainless steel sheet constituting the test piece of the patch was stretched at a speed of 1000 mm / min in an atmosphere of 23°C and 50% RH immediately after the patch was attached, and the strength of peeling the stainless steel sheet was defined as the adhesive force P at 400% stretching. 400 .

[0019] It should be noted that the adhesive tape of the present invention is not limited to a double-sided tape that must have an adhesive layer on both sides of the substrate layer, or a (double-sided) tape that must have a release liner, as long as it has an adhesive layer on at least one side of the substrate layer. 2 ) and the cleavage adhesion force P 400 (N / cm 2 ) and in the method for manufacturing a double-sided tape having an adhesive layer and / or a release liner on both sides of the substrate layer, the process of providing the adhesive layer on both sides of the substrate layer can be appropriately changed to the process of providing the adhesive layer only on one side of the substrate layer. In addition, the initial cleavage adhesion and the adhesion when stretched 400% have nothing to do with the structure of having adhesive layers on both sides of the substrate layer, and mainly depend on the characteristics of the adhesive layer and the adhesion between the adhesive layer and the substrate layer. Therefore, the above-mentioned relationship (i) as the characteristics of the double-sided tape and the above-mentioned evaluation method can of course also be applied to single-sided tape.

[0020] In the present invention, the adhesive force P when stretched 400% is 400 (N / cm2 ) is preferably 0.001 to 70 N / cm 2 , more preferably 0.1 to 40 N / cm 2 , more preferably 1 to 30 N / cm 2 If the above adhesion P 400 0.001~70N / cm 2 , it is easy to take into account both removability and adhesion. As P in the above relation (i) 400 / P0 is 0.9 or less. It is preferably 0.001 to 0.7, more preferably 0.01 to 0.6, and further preferably 0.01 to 0.3. By making the above relational expression (i) 0.9 or less, excellent removability can be achieved in a state where a part of the adhesive tape has been peeled off from the adherend.

[0021] In the pressure-sensitive adhesive tape of the present embodiment, by having any one or more of the following requirements (a) to (f), there is a tendency that the condition of the above-mentioned relational expression (i) is easily satisfied. (a) The storage modulus G' (23°C) of the adhesive layer is 1.0×10 5 ~1.0×10 7 Pa. (b) Adding fillers to the adhesive layer. (c) The adhesive layer is an adhesive containing a styrene-based block copolymer. (d) The adhesive layer is an adhesive containing an acrylic block copolymer. (e) The filler contained in the adhesive layer is a silicon-based filler. (f) The adhesive layer contains a tackifying resin. By satisfying the above (a), (c), (d) or (f), the recovery force of the adhesive layer after the adhesive tape is stretched is low, so that the adhesive tape after being stretched 400% is difficult to recover to normal state, and the adhesive force P can be reduced. 400 In addition, it is easy to achieve a high load holding force. In addition, by satisfying the above (b), the filler in the adhesive layer is exposed to the surface when the adhesive tape is stretched, and the adhesive force P in the above relational expression (i) can be reduced. 400 In particular, by combining with the above-mentioned requirements (a), (c), (d) or (f), the state where the filler in the adhesive layer is exposed on the surface can be maintained for a long time, and thus a synergistic effect can be exerted. By satisfying the above-mentioned condition (e), re-adhesion to an adherend can be effectively suppressed, and slip properties can be imparted to the pressure-sensitive adhesive layer during re-peeling, thereby improving re-peelability. The reason why "removability in a state where a portion of the pressure-sensitive adhesive tape has been peeled off from an adherend" is improved by satisfying the above relationship (i) is complicatedly related to the above requirements (a) to (f), etc., and therefore the details of the mechanism are not yet clear. However, it is currently believed to be as follows.

[0022] By stretching the adhesive tape, the filler in the adhesive protrudes to the adhesive surface, so that adhesion is reduced. In addition, by using an adhesive with an elastic modulus, this state can be maintained for a long time. In addition, by using a high filler of sliding property like a silicon-based filler, stretching becomes easy. Based on the above reasons, it is believed that the excellent re-peelability can be brought into play under the state that a part of the adhesive tape has been peeled off from the adherend.

[0023] It should be noted that the adhesive tape of the present invention is provided with an adhesive layer abutting against the substrate layer on at least one side of the substrate layer. In addition, the adhesive tape of the present invention can be provided with 2 adhesive layers abutting against the substrate layer on both sides of the substrate layer as required, in which case, the 2 adhesive layers can be identical to each other, or can be different from each other. It should be noted that the adhesive tape of the present invention is not only a general term for an adhesive tape that is provided with an adhesive layer on one or both sides of the substrate layer and is rolled into a roll, but also includes an adhesive tape that is plate-shaped and bonded with a release liner and is provided with an adhesive layer on one or both sides of the substrate layer.

[0024] Hereinafter, the base material layer and the adhesive layer constituting the adhesive tape of the present invention will be described in detail. [Base material layer] In this embodiment, the adhesive tape comprises at least one adhesive layer and a base layer in contact with the adhesive layer, and the base layer has a breaking stress of 1 to 100 MPa and a breaking elongation of 400 to 3000%.

[0025] In this embodiment, the substrate layer is not particularly limited as long as it has the above-mentioned properties, and can be appropriately selected from known materials that can be used for adhesive tapes, preferably including the following substrate materials, and can also further include other components as needed. The substrate layer can be a single-layer structure, or it can be a 2-layer, 3-layer, or a multi-layer structure of more than 100 layers.

[0026] In the present embodiment, the fracture stress of the substrate layer is 1 to 100 MPa, preferably 10 to 90 MPa, more preferably 15 to 90 MPa, further preferably 30 to 90 MPa, and further preferably 50 to 90 MPa. By making the fracture stress above 1 MPa, when the adhesive tape is peeled off from the adherend, even if the operator stretches it, the adhesive tape can be peeled off from the adherend without breaking. In addition, by making the fracture stress below 90 MPa, it is possible to avoid the stress when the operator stretches the adhesive tape becoming too large.

[0027] The breaking stress of the substrate layer refers to the stress value measured when the substrate layer is punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0028] The breaking stress can be adjusted by selecting an appropriate material and applying stretching or the like during the manufacturing process of the base material layer.

[0029] In the present embodiment, the elongation at break of the substrate layer is 400 to 3000%, preferably 500 to 2500%, more preferably 530 to 1700%, further preferably 560 to 1300%, and further preferably 600 to 1200%. By making the elongation at break 400% or more, even when the adhesive tape is firmly bonded to the adherend, the stress when peeling the adhesive tape will not become too large. In addition, by making the elongation at break 3000% or less, when peeling the adhesive tape, the stretching distance will not become too long, and the operation can be performed in a small space.

[0030] The elongation at break of the substrate layer refers to the tensile elongation measured when the substrate layer is punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and stretched in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0031] The elongation at break can be adjusted by selecting an appropriate material and applying stretching or the like in the production process of the base material layer.

[0032] In this embodiment, the 50% modulus of the substrate layer is preferably 0.1 to 5 MPa, more preferably 0.5 to 4.5 MPa, and further preferably 1 to 4 MPa. By making the 50% modulus 0.1 MPa or more, when a load is applied to the adhesive tape and the adherend, the undesirable situation caused by shape deformation such as offset can be suppressed. In addition, by making the 50% modulus 5 MPa or less, in the initial stage of peeling the adhesive tape from the adherend, the operator can stretch it with a relatively light force.

[0033] The 50% modulus of the substrate layer refers to the stress value measured when the substrate layer is punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and stretched in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0034] The 50% modulus can be adjusted by selecting an appropriate material and applying stretching or the like during the production process of the base material layer.

[0035] In the present embodiment, the rubber hardness of the substrate layer is preferably 25 to 90A, more preferably 30 to 85A, and further preferably 35 to 80A. By making the rubber hardness 25A or more, the adhesive tape can be prevented from breaking when the adhesive tape is stretched and peeled. In addition, by making the rubber hardness 90A or less, the substrate layer can be softened, for example, when the adherend to which the adhesive tape is attached is dropped, the adhesive tape easily absorbs the impact, and the adherend can be protected from the impact (the impact resistance of the adhesive tape can be improved).

[0036] The rubber hardness of the base material layer is Shore A hardness, which refers to a value measured in accordance with JIS K 6253 using a durometer (spring type rubber durometer) (model: GS-719G, manufactured by TECLOCK CO., LTD.).

[0037] In addition, the rubber hardness can be adjusted by selecting appropriate materials, for example, by changing the molecular weight of the resin, or by changing the monomer unit when a styrene monomer unit is included.

[0038] The average thickness of the substrate layer is 10 to 500 μm, preferably 30 to 250 μm, and more preferably 50 to 200 μm. By setting the thickness to 10 μm or more, the strength of the adhesive tape can be ensured; and by setting the thickness to 500 μm or less, it is possible to avoid the adhesive tape being too thick and difficult to stretch.

[0039] In addition, in this specification, "the thickness of a base material layer" means the average value which averaged the thickness of arbitrary 5 points in a base material layer measured using TH-104 paper and film thickness measuring instrument (made by Tester Sangyo Co., Ltd.).

[0040] As the ratio of the thickness of the adhesive layer and the substrate layer, there is no particular restriction, and it can be appropriately selected according to the purpose, and the ratio of the thickness of the adhesive layer represented by [the thickness of the adhesive layer / the thickness of the substrate layer] relative to the thickness of the substrate layer is preferably 1 / 6 to 6 / 1, more preferably 1 / 3 to 3 / 1, and further preferably 1 / 2 to 2 / 1. If the ratio of the thickness of the adhesive layer relative to the thickness of the substrate layer is within a preferred range, the excellent adhesion and re-peelability (peeling ease) of the adhesive tape can be obtained. On the other hand, if the ratio is greater than 5 / 1, it is possible that only the adhesive layer remains in the adherend in the re-peeling process of the adhesive tape. In addition, if the ratio is less than 1 / 5, then in the case where the surface of the adherend is a concave-convex shape, etc., there is the possibility that the adhesive layer cannot follow the surface so that the bonding strength is reduced.

[0041] The material of the substrate layer is not particularly limited as long as a substrate layer having the above-mentioned specific properties can be obtained, and examples thereof include the following substances as main components: styrene resins such as styrene-isoprene copolymer, styrene-isoprene-styrene copolymer, styrene-isoprene-butadiene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-ethylene-butylene copolymer, styrene-ethylene-propylene copolymer; polyurethane resins such as ester polyurethane and ether polyurethane; polyolefin resins such as polyethylene and polypropylene; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polystyrene; polycarbonate; polymethylpentene; polysulfone; polyetheretherketone; polyethersulfone; polyetherimide; polyimide film; fluororesin; nylon; acrylic resin, etc. These can be used alone or in combination of two or more; preferably in combination of two or more.

[0042] Among them, styrene resins or polyurethane resins are preferred because they can easily provide suitable breaking stress and breaking elongation; styrene resins are more preferred, and the combination of styrene-isoprene copolymers and styrene-isoprene-styrene copolymers is particularly preferred.

[0043] In addition, the main component of the material of the base material layer refers to the case where the main component represents 50 mass% or more with respect to the total material of the base material layer.

[0044] The styrene resin is a thermoplastic resin, so it has excellent formability in extrusion molding, injection molding, etc., and is easy to form a substrate layer. In addition, the styrene resin is easy to obtain particularly excellent elongation at break in the resin group generally referred to as thermoplastic resins, and can be suitably used as a substrate layer of an adhesive sheet.

[0045] Therefore, in the material of the substrate layer, the proportion (mass) of the styrene resin relative to the total resin components (or the total materials) is preferably 50 to 100%, more preferably 60 to 100%, further preferably 65 to 100%, and particularly preferably 70 to 100%. By making the proportion of the styrene resin within the above preferred range, a substrate layer having excellent elongation at break and stress at break can be obtained.

[0046] The styrene resin may be, for example, a styrene resin having a single structure of a linear structure, a branched structure or a multi-branched structure, or a mixture of styrene resins of different structures. A styrene resin having a rich linear structure can impart excellent elongation at break to the substrate layer. On the other hand, a styrene resin having a branched structure or a multi-branched structure and having a styrene block at the molecular end can adopt a pseudo cross-linked structure and impart excellent cohesive force. Therefore, the styrene resin is preferably used in a mixture according to the desired mechanical properties.

[0047] As a styrene resin, it is preferred to use a styrene resin containing a structural unit shown in the following chemical formula (A) in a range of 5 to 50% by mass relative to the total mass of the styrene resin, more preferably a styrene resin containing a structural unit shown in the following chemical formula (A) in a range of 5 to 40% by mass, further preferably a styrene resin containing a structural unit shown in the following chemical formula (A) in a range of 10 to 30% by mass, and particularly preferably a styrene resin containing a structural unit shown in the following chemical formula (A) in a range of 15 to 25% by mass. By making the ratio of the structural unit shown in the following chemical formula (A) relative to the total mass of the styrene resin within the preferred range, it is easy to obtain an elongation at break and a breaking stress within a suitable range. It should be noted that the * in the following chemical formula (A) represents a bond position with other atoms, and the same is true in the chemical formula (B) and chemical formulas (1) to (6) described later. [Chemistry 2]

[0048] When a styrene-based resin is used in combination with a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer, the content of the styrene-isoprene copolymer is preferably 0 to 80% by mass, more preferably 0 to 70% by mass, further preferably 0 to 50% by mass, and particularly preferably 0 to 30% by mass, relative to the total mass of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer. If the content of the styrene-isoprene copolymer is within the preferred range, thermal durability can be achieved while maintaining excellent elongation at break and stress at break.

[0049] In addition, as the styrene-isoprene copolymer, it is preferred to use a styrene-isoprene copolymer having a weight average molecular weight of 10,000 to 800,000 as measured by gel permeation chromatography (GPC) in terms of standard polystyrene, more preferably 30,000 to 500,000, and even more preferably 50,000 to 300,000. By making the weight average molecular weight of the styrene-isoprene copolymer within the preferred range, the fluidity during heating and the compatibility during solvent dilution can be ensured, so that the workability in the manufacturing process is good, and a substrate layer having heat durability can be obtained, which is preferred.

[0050] Here, the weight average molecular weight of the styrene-isoprene copolymer measured by the GPC method is a standard polystyrene conversion value measured using a GPC apparatus (SC-8020, manufactured by Tosoh Corporation), and the measurement conditions are as follows. "Measurement conditions" - Sample concentration: 0.5 mass% (tetrahydrofuran solution) Sample injection volume: 100μL ·Eluent: Tetrahydrofuran Flow rate: 1.0mL / min ·Measurement temperature: 40℃ Main column: TSKgel (registered trademark) GMHHR-H (20) 2 pieces Guard column: TSKgel HXL-H Detector: Differential refractometer · Standard polystyrene molecular weight: 10,000 to 20,000,000 (manufactured by Tosoh Corporation) There are no particular restrictions on the production method of styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, and mixtures of styrene-isoprene copolymers and styrene-isoprene-styrene copolymers, and they can be appropriately selected from conventionally known production methods. Block copolymers can be obtained by anionic living polymerization, and a coupling agent can be added as needed to react them.

[0051] Specifically, the method for producing the styrene-isoprene copolymer is not particularly limited and may be appropriately selected from conventionally known production methods. Examples thereof include a method of sequentially polymerizing a styrene block and an isoprene block by an anionic living polymerization method.

[0052] There are no particular restrictions on the method for producing the styrene-isoprene-styrene copolymer, and it can be appropriately selected from conventionally known production methods, for example, a method of sequentially polymerizing a styrene block and an isoprene block by an anionic living polymerization method, a method of producing a block copolymer having a living polymerizable active terminal and then reacting with a coupling agent to couple the block copolymer, etc.

[0053] The method for producing the mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. For example, there can be mentioned a method of mixing the styrene-isoprene copolymer produced by the above method with a styrene-isoprene-styrene copolymer.

[0054] In addition, as a method for producing a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer, they can be simultaneously produced as a mixture in one polymerization step.

[0055] As a more specific embodiment, by anionic living polymerization, first, styrene monomers are polymerized in a polymerization solvent using an anionic polymerization initiator to form polystyrene blocks having living polymerizable active ends. Second, isoprene is polymerized from the living polymerizable active ends of the polystyrene blocks to obtain styrene-isoprene diblock copolymers having living polymerizable active ends. Third, a portion of the styrene-isoprene diblock copolymers having living polymerizable active ends is reacted with a coupling agent to form coupled styrene-isoprene-styrene block copolymers. Fourth, a polymerization terminator is used to inactivate the living polymerizable active ends of the remaining portion of the styrene-isoprene diblock copolymers having living polymerizable active ends to form styrene-isoprene diblock copolymers.

[0056] The polyurethane resin is not particularly limited and can be appropriately selected according to the purpose, but preferably has a softening point of 40° C. or higher, and more preferably has a softening point of 50° C. or higher. The upper limit of the softening point is preferably 100° C. or lower. The “softening point” refers to a value measured according to JIS K 2207 (ring and ball method) (hereinafter, the softening point is measured by the same method).

[0057] As the polyurethane resin, a reaction product of a polyol (b1-1) and a polyisocyanate (b1-2) can be preferably used.

[0058] As polyol (b1-1), there is no particular limitation and it can be appropriately selected according to the purpose, for example, polyester polyol, polyether polyol, polycarbonate polyol, acrylic polyol etc. can be mentioned. They can be used alone or in combination of two or more. Among them, as polyol (b1-1), polyester polyol and polyether polyol can obtain the mechanical properties of the substrate layer, so it is preferred. In the substrate layer, polyester polyol is preferably used when heat resistance is required, and polyether polyol is preferably used when water resistance and biodegradability resistance are required.

[0059] Examples of the polyester polyol include polyesters obtained by esterification reaction of a low molecular weight polyol and a polycarboxylic acid, polyesters obtained by ring-opening polymerization of a cyclic ester compound such as ε-caprolactone, and copolymerized polyesters thereof.

[0060] Examples of low molecular weight polyols that can be used in the production of the polyester polyol include aliphatic alkylene glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, 1,3-butanediol, and cyclohexanedimethanol having a weight average molecular weight of about 50 to 300.

[0061] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; and anhydrides or esters thereof.

[0062] Examples of the polyether polyol include polyether polyols obtained by addition-polymerizing an alkylene oxide using one or more compounds having two or more active hydrogen atoms as an initiator.

[0063] As the polycarbonate polyol, for example, a polycarbonate polyol obtained by reacting carbonate and / or phosgene with a low molecular weight polyol described below can be used.

[0064] Examples of the carbonate ester include methyl carbonate, dimethyl carbonate, ethyl carbonate, diethyl carbonate, cyclic carbonate, and diphenyl carbonate.

[0065] Examples of the low molecular weight polyol that can be used to produce the polycarbonate polyol and can react with carbonate and / or phosgene include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, tripropylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 2,5-hexanediol, and 1,7-heptanediol. , 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,4-cyclohexanedimethanol, hydroquinone, resorcinol, bisphenol A, bisphenol F, 4,4'-biphenol, etc.

[0066] There is no particular limitation on the polyisocyanate (b1-2), and it can be appropriately selected according to the purpose. For example, alicyclic polyisocyanate, aliphatic polyisocyanate, aromatic polyisocyanate, etc. can be used, and alicyclic polyisocyanate, etc. can be mentioned. They can be used alone or in combination of two or more.

[0067] Examples of the alicyclic polyisocyanate include isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, 2,4-methylcyclohexane diisocyanate, 2,6-methylcyclohexane diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, 2,6-norbornane diisocyanate, dimer acid diisocyanate, and bicycloheptane triisocyanate. These may be used alone or in combination of two or more.

[0068] There are no particular restrictions on the method for producing the polyurethane resin (b1) by reacting a polyol (b1-1) with a polyisocyanate (b1-2), and the method can be appropriately selected from conventionally known production methods. For example, the following method can be cited: after heating the polyol (b1-1) put into a reaction container under normal pressure or reduced pressure to remove moisture, the polyisocyanate (b1-2) is supplied all at once or in batches to react.

[0069] The reaction of the polyol (b1-1) and the polyisocyanate (b1-2) is preferably carried out within the range of 1.0 to 20.0 of the equivalent ratio of the isocyanate group (NCO) of the polyisocyanate (b1-2) to the hydroxyl group (OH) of the polyol (b1-1) (NCO / OH equivalent ratio), more preferably within the range of 1.1 to 13.0, further preferably within the range of 1.2 to 5.0, and particularly preferably within the range of 1.5 to 3.0.

[0070] The reaction conditions of the polyol (b1-1) and the polyisocyanate (b1-2) are not particularly limited and can be appropriately selected in consideration of various conditions such as safety, quality, and cost. The reaction temperature is preferably 70 to 120° C., and the reaction time is preferably 30 minutes to 5 hours.

[0071] When the polyol (b1-1) and the polyisocyanate (b1-2) are reacted, a catalyst such as a tertiary amine catalyst or an organic metal catalyst may be used as necessary.

[0072] In addition, the reaction may be performed in the absence of a solvent or in the presence of an organic solvent.

[0073] The organic solvent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include ester solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone, methyl butyl ketone, and cyclohexanone; ether ester solvents such as methyl cellosolve acetate and butyl cellosolve acetate; aromatic hydrocarbon solvents such as toluene and xylene; amide solvents such as dimethylformamide and dimethylacetamide, etc. These solvents can be used alone or in combination of two or more.

[0074] The organic solvent can be removed by an appropriate method such as heating under reduced pressure, drying under normal pressure, etc. during the production process of the polyurethane resin (b1) or after the production of the polyurethane (b1).

[0075] There are no particular restrictions on other components in the substrate layer, and they can be appropriately selected within the range that does not damage the properties of the adhesive tape, such as tackifying resins; polymer components other than the materials of the substrate layer; additives such as crosslinking agents, anti-aging agents, ultraviolet absorbers, fillers, polymerization inhibitors, surface regulators, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, silica beads, and organic beads; inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, and antimony pentoxide, etc. These can be used alone or in combination of two or more.

[0076] The content of other components in the base material layer can be appropriately selected within a range that does not impair the properties of the pressure-sensitive adhesive tape.

[0077] The tackifier resin can be used for the purpose of improving the adhesion between the adhesive layer and the base layer of the adhesive tape or improving the heat resistance.

[0078] The tackifier resin is not particularly limited and may be appropriately selected depending on the purpose. A tackifier resin having a softening point of 80° C. or higher is preferred, 90° C. or higher is more preferred, 100° C. or higher is further preferred, and 110° C. or higher is particularly preferred.

[0079] As the tackifier resin, for example, the tackifier resins described in the item "rubber-based binder resin" described later can be used, and the preferred aspects and the like are also the same.

[0080] As antioxidant, there is no particular restriction, and can be suitably selected according to the purpose from known antioxidants, for example, phenolic antioxidants, phosphorus antioxidants (sometimes also referred to as "processing stabilizers"), amine antioxidants, imidazole antioxidants, etc. can be cited. They can be used alone or in combination of two or more. Among them, preferred phenolic antioxidants and phosphorus antioxidants, when used in combination, can effectively improve the heat resistance stability of substrate materials, and as a result, can obtain an adhesive tape that maintains good initial adhesion and possesses further excellent heat durability, so it is preferred. It should be noted that phosphorus antioxidants sometimes change color (yellowing) slightly over time under high temperature environment, and therefore, its usage amount is preferably appropriately set in consideration of the balance between initial adhesion, heat durability and preventing discoloration.

[0081] As phenolic antioxidants, phenolic compounds with sterically hindered groups can generally be used, and monophenol type, bisphenol type, and polyphenol type are representative. As specific examples, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(6-tert-butyl-3-methylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), tetrakis-[methylene propionate-3-(3'5'-di-tert-butyl-4-hydroxyphenyl) ester] methane, propionic acid n-octadecyl-3-(4'-hydroxy-3'5'-di-tert-butylphenyl) ester, etc. can be cited. They can be used alone or in combination of two or more.

[0082] The amount of the phenolic antioxidant used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 0.1 to 5 parts by mass relative to 100 parts by mass of the substrate material. When used in the range of 0.5 to 3 parts by mass, the heat resistance stability of the substrate material can be effectively improved. As a result, an adhesive tape that maintains good initial adhesion and has further excellent thermal durability can be obtained.

[0083] "Adhesive layer" The adhesive layer in the present invention contains an adhesive resin and may contain a tackifier resin and / or a filler as required. In addition, the adhesive layer in the present invention is formed from an adhesive composition containing an adhesive resin described below and a tackifier resin, a filler and / or other components added as required.

[0084] In this embodiment, the storage modulus G' (23°C) of the adhesive layer is preferably 1.0×10 5 ~1.0×10 7 Pa, more preferably 1.0×10 5 ~1.0×10 6Pa, more preferably 1.5×10 5 ~9.0×10 5 Pa, more preferably 2.0×10 5 ~8.0×10 5 Pa. The storage modulus G' (23°C) of the adhesive layer can achieve a high balance between initial adhesion, high load holding power and time-dependent removability. In addition, by making the breaking point stress of the adhesive layer within the above range, it is easy to follow the deformation of the adherend, easy to obtain excellent bonding strength, and can also ensure the dimensional stability of the substrate layer, so that suitable attachment workability can be obtained.

[0085] The 25% elongation stress of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 0.04 to 0.4 MPa, more preferably 0.05 to 0.1 MPa. If the 25% elongation stress of the adhesive layer is within the preferred range, a bonding strength suitable for the adhesive tape can be obtained, and the adhesive tape can be pulled and peeled relatively easily even when the adhesive tape is stretched and peeled. On the other hand, if the 25% elongation stress of the adhesive layer is less than 0.04 MPa, the adhesive tape may sometimes peel off when a load in the shear direction of the adhesive tape is generated while fixing hard adherends to each other. If it exceeds 0.4 MPa, when the adhesive tape is pulled and peeled, the force required to stretch the adhesive tape may sometimes become too large.

[0086] The 25% elongation stress of the adhesive layer refers to the stress value measured when the adhesive layer is punched into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a stretching speed of 300 mm / min under the conditions of a measuring atmosphere of 23°C and 50% RH using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) and elongated by 25%.

[0087] The breaking stress of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 0.5 to 2.1 MPa, more preferably 1.0 to 2.1 MPa. If the breaking stress of the adhesive layer is within the preferred range, the adhesive tape can be prevented from rupturing when the adhesive tape is stretched and peeled off, and the load used to stretch the adhesive tape will not become too large, so the re-peeling operation by stretching and peeling becomes easy. On the other hand, if the breaking stress of the adhesive layer is lower than 0.5 MPa, sometimes residual glue caused by cohesive failure of the adhesive layer will occur when the adhesive tape is stretched and peeled off; if it exceeds 2.1 MPa, sometimes sufficient adhesion cannot be obtained. It should be noted that the force required to stretch the adhesive tape to deform it also depends on the thickness of the adhesive tape. For example, when you want to stretch and peel off an adhesive tape with a thick thickness and high breaking stress, it is sometimes impossible to fully stretch it and thus cannot be peeled off.

[0088] The breaking stress of the adhesive layer is the stress value measured when the adhesive layer is punched into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a stretching speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0089] The elongation at break of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 450 to 1300%, more preferably 500 to 1200%, and further preferably 600 to 1100%. By making the elongation at break of the adhesive layer within the above preferred range, both appropriate adhesion and removability (ease of peeling) can be taken into account.

[0090] The elongation at break of the adhesive layer refers to the tensile elongation measured when the adhesive layer is punched into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a tensile speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measurement atmosphere of 23°C and 50% RH, and the layer is stretched to break.

[0091] The average thickness of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 1 to 200 μm, more preferably 10 to 150 μm, further preferably 30 to 120 μm, and particularly preferably 40 to 100 μm. The "average thickness of the adhesive layer" refers to the thickness of the adhesive layer on one side of the adhesive tape. In the case where the adhesive tape has adhesive layers on both sides, the average thickness of the adhesive layer on one side may be the same as or different from the average thickness of the adhesive layer on the other side, and preferably they are the same thickness.

[0092] It should be noted that in this specification, the average thickness of the adhesive layer can be measured by the following method. That is, after the adhesive tape is immersed in liquid nitrogen for 1 minute, tweezers are used to bend and cut the adhesive tape in the liquid nitrogen with the width direction of the adhesive tape as a fold, and a slice is made for observing the cut surface in the thickness direction of the adhesive tape. After the slice is restored to room temperature in a dryer, it is fixed to the sample table in a manner that the electron beam is incident vertically with respect to the cut surface, and the cut surface is observed using an electron microscope. Based on the magnification of the electron microscope, the thickness of the adhesive layer in the adhesive tape at 10 locations is measured, and the arithmetic mean thereof is taken as the thickness of the adhesive layer. It should be noted that the thickness of the adhesive layer is the length measured from the surface on one side to the surface on the other side along the stacking direction.

[0093] <Binder resin> The binder resin used in the adhesive layer of the present invention preferably includes, as the main component of the binder resin, an acrylic binder resin containing an acrylic block copolymer or an aromatic vinyl binder resin containing a styrene block copolymer. The "main component of the binder resin" in this specification refers to the main component of the resin component contained in the binder resin (typically a component containing more than 50% by mass).

[0094] The acrylic block copolymer preferably accounts for 30 to 100% by mass, and more preferably accounts for 50 to 95% by mass, based on the entire binder resin used in the adhesive layer of the present invention.

[0095] In the adhesive layer of the present invention, if the content of the acrylic block copolymer is 30% by mass or more, it is easy to take into account both removability and high load holding power. In addition, relative to the entire binder resin used in the adhesive layer of the present invention, preferably the styrene block copolymer accounts for 30 to 100% by mass, and more preferably the styrene block copolymer accounts for 50 to 100% by mass.

[0096] In the adhesive layer of the present invention, when the content of the styrene-based block copolymer is 30% by mass or more, it is easy to achieve both removability and high load holding power.

[0097] <<Acrylic adhesive resin containing acrylic block copolymer>> The acrylic block copolymer in the present invention is preferably a triblock copolymer having a repeating unit represented by the general formula (1): [Chemistry 3] (In the above general formula (1), A, B and C each independently represent a repeating unit, A and C each independently represent an alkyl methacrylate monomer unit, B represents an alkyl acrylate monomer unit, p, q and r each independently represent the degree of polymerization of each monomer unit, A and C may be the same, or may be an alkyl methacrylate monomer unit with a different chemical structure. In the above general formula (1), * represents the bonding position with other atoms.)

[0098] In the above general formula (1), A and C represent repeating units different from B, and represent alkyl methacrylate monomer units. In addition, A and C are each independent and may be the same alkyl methacrylate monomer units, or may be alkyl methacrylate monomer units having different chemical structures. The "alkyl methacrylate monomer unit" in this specification refers to a structural unit derived from an alkyl methacrylate monomer when an alkyl methacrylate monomer is (co)polymerized or graft-polymerized, i.e., a repeating unit derived from a methacrylate monomer. The alkyl methacrylate monomer unit in the present invention is preferably represented by the following general formula (2): [Chemistry 4] (In the above general formula (2), R 1 represents an alkyl group having 1 to 12 carbon atoms, in which one or more hydrogen atoms may be substituted by R 2 Substitution, the substituent R 2 represents a halogen atom, an amino group, or a cyano group. ).

[0099] In the above general formula (2), from the viewpoint of removability and high load holding power, R 1 An alkyl group having 1 to 12 carbon atoms is preferred, an alkyl group having 1 to 4 carbon atoms is more preferred, and an alkyl group having 1 to 2 carbon atoms is further preferred.

[0100] In the general formula (2), the alkyl group having 1 to 12 carbon atoms may be linear, branched, or cyclic. From the viewpoint of adhesive strength, the alkyl group is preferably linear or branched, and more preferably linear.

[0101] In the general formula (2), examples of the alkyl group having 1 to 12 carbon atoms include linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, hexyl, octyl, nonyl, decyl, undecyl, and dodecyl; and cyclic alkyl groups such as cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, dicyclopentyl, and adamantyl. Among them, from the viewpoint of removability and high load holding power, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, or tert-butyl is preferred, and methyl, ethyl, and propyl are more preferred.

[0102] In the above general formula (2), examples of the alkyl group having 1 to 4 carbon atoms include linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, and tert-butyl; and cyclic alkyl groups such as cyclobutyl. From the viewpoint of removability and high load holding power, the alkyl group having 1 to 4 carbon atoms is preferably methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, and tert-butyl, and more preferably methyl.

[0103] Therefore, the preferred R in the above general formula (2) is 1 It is any alkyl group selected from the group consisting of methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl and cyclobutyl, and one or two or more hydrogen atoms in the alkyl group may be substituted by a halogen atom, an amino group or a cyano group.

[0104] In the present embodiment, for example, the methacrylate alkyl ester monomer is not particularly limited, and examples thereof include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, pentadecyl methacrylate, cyclohexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, 2-hexyldecyl methacrylate, etc. Among them, methyl methacrylate is preferred from the viewpoint of high load holding power and disassembly properties.

[0105] In the general formula (1), B represents a repeating unit different from A and C, and represents an alkyl acrylate monomer unit. The "alkyl acrylate monomer unit" in this specification refers to a structural unit derived from an alkyl acrylate monomer when an alkyl acrylate monomer is (co)polymerized or graft-polymerized, that is, a repeating unit derived from an acrylate monomer. The alkyl acrylate monomer unit in the present invention is preferably represented by the following general formula (3): [Chemistry 5] (In the above general formula (3), R 3 represents an alkyl group having 1 to 12 carbon atoms, wherein one or more hydrogen atoms in the alkyl group may be substituted by a substituent R 4 Substitution, the substituent R 4 represents a halogen atom, an amino group, or a cyano group. ).

[0106] In the above general formula (3), from the viewpoint of adhesiveness, R 3 An alkyl group having 1 to 20 carbon atoms is more preferred, and an alkyl group having 4 to 8 carbon atoms is further preferred.

[0107] In the above general formula (3), the alkyl group having 1 to 12 carbon atoms may be linear, branched or cyclic; from the viewpoint of adhesion, it is preferably linear or branched. In addition, examples of the alkyl group having 1 to 12 carbon atoms and the alkyl group having 4 to 8 carbon atoms are the same as the examples of the alkyl group having 1 to 12 carbon atoms in the above general formula (2).

[0108] Therefore, the preferred R in the above general formula (3) is 3It is a straight-chain or branched alkyl group such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, hexyl, octyl, nonyl, decyl, undecyl or dodecyl, or a cyclic alkyl group such as cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, dicyclopentyl or adamantyl; one or more hydrogen atoms in these alkyl groups may be substituted by a halogen atom, an amino group or a cyano group.

[0109] In the present embodiment, examples of the acrylic acid alkyl ester monomer include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, etc. Among them, n-butyl acrylate, 2-ethylhexyl acrylate, and copolymers thereof are preferred from the viewpoint of achieving both adhesive strength and removability.

[0110] In the above general formula (1), p, q and r each independently represent the degree of polymerization of each monomer unit. The respective values ​​of p, q and r are related to the molecular weight, etc. p / (p+q+r) is preferably 0.02 to 0.40, and more preferably 0.05 to 0.37. q / (p+q+r) is preferably 0.20 to 0.95, and more preferably 0.25 to 0.90. r / (p+q+r) is preferably 0.02 to 0.40, and more preferably 0.05 to 0.37.

[0111] In this embodiment, the acrylic block copolymer preferably has a repeating unit represented by the following general formula (4): [Chemistry 6] (In the above general formula (4), R 1 and R 5 Each independently represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group may be substituted by R 2 Substitution, the substituent R 2 represents a halogen atom, an amino group or a cyano group, R 3 represents an alkyl group having 1 to 12 carbon atoms, in which one or more hydrogen atoms may be substituted by R 4 Substitution, the substituent R 4 represents a halogen atom, an amino group, or a cyano group, and p, q, and r each independently represent the degree of polymerization of each monomer unit. ).

[0112] In the above general formula (4), R 1 It can be applied to R in the above general formula (2) 1 In the above general formula (4), R 3It can be applied to R in the above general formula (3) 3 In the above general formula (4), R 5 It can be applied to R in the above general formula (2) 1 In the above general formula (4), p, q and r can be applied in the same form as p, q and r in the above general formula (1). In the above general formula (4), R 1 and R 5 It can be the same or different.

[0113] In this embodiment, when the triblock copolymer is represented by the above general formula (4), R 1 Preferably, R is selected from a linear or branched alkyl group such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, and a cyclobutyl group. 3 Preferably, R is selected from methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, hexyl, octyl, nonyl, decyl, or undecyl. 5 Preferably, it is selected from a linear or branched alkyl group such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, and a cyclobutyl group, and preferably p / (p+q+r) is 0.02 to 0.40, q / (p+q+r) is 0.20 to 0.95, and r / (p+q+r) is 0.02 to 0.40.

[0114] In the triblock copolymer of the present invention, it is preferred that A and C in the general formula (1) are the same. Specifically, when the triblock copolymer has a repeating unit represented by the general formula (4), it is preferred that R 1 With R 5 For the same group, p / (p+q+r) is 0.02-0.40, q / (p+q+r) is 0.20-0.95, and r / (p+q+r) is 0.02-0.40. In the triblock copolymer having the repeating unit represented by the general formula (1), when A and C are the same (ABA type triblock copolymer), a higher elastic modulus can be ensured, and therefore, it is easier to ensure that the adhesive force exhibits excellent high load holding power, removability over time, and storage stability.

[0115] The acrylic block copolymer in the present invention is preferably a diblock copolymer having a repeating unit represented by the general formula (5): [Chemistry 7] (In the above general formula (5), D and E each independently represent a repeating unit, D represents an alkyl methacrylate monomer unit, E represents an alkyl acrylate monomer unit, and s and t each independently represent the degree of polymerization of each monomer unit. In the above general formula (5), * represents the bond position with other atoms.)

[0116] In the present embodiment, the acrylic block copolymer used in the adhesive resin is preferably selected from at least one of the triblock copolymers shown in the above-mentioned general formula (1) and the triblock copolymers shown in the above-mentioned general formula (5). In particular, if a triblock copolymer and a diblock copolymer are used in the adhesive resin, it is easier to ensure high elastic modulus and initial adhesion, and therefore it is easier to ensure high load holding power, time-dependent re-peelability and initial adhesion. In particular, when fillers are included in the adhesive layer, after the adhesive tape is stretched, compared with the form in which fillers are not present in the adhesive layer, the state in which the fillers in the adhesive layer are exposed to the surface can be maintained for a long time, so that the excellent synergistic effect is exerted in a complementary manner with the effect of the filler. The alkyl methacrylate monomer units and alkyl acrylate monomer units in the general formula (5) can be applied in the same form as the alkyl methacrylate monomer units and alkyl acrylate monomer units in the general formula (1).

[0117] The diblock polymer in the present invention preferably has a repeating unit represented by the following general formula (6): [Chemistry 8] (In the above general formula (6), R 6 represents an alkyl group having 1 to 12 carbon atoms, in which one or more hydrogen atoms may be substituted by R 8 Substitution, the substituent R 8 represents a halogen atom, an amino group, or a cyano group, R 7 represents an alkyl group having 1 to 12 carbon atoms, in which one or more hydrogen atoms may be substituted by R 9 Substitution, the substituent R 9 represents a halogen atom, an amino group, or a cyano group, and s and t each independently represent the degree of polymerization of each monomer unit. ).

[0118] In the above general formula (6), R 6 It can be applied to R in the above general formula (2) 1 In the above general formula (6), R 7 It can be applied to R in the above general formula (3) 3 In the above general formula (6), s and t can be in the same form as p and q in the above general formula (1).

[0119] In this embodiment, the weight average molecular weight Mw of the diblock copolymer is preferably 50,000 to 300,000, and the number average molecular weight Mn is preferably 50,000 to 300,000. The weight average molecular weight can be measured by the method for measuring the weight average molecular weight of the triblock copolymer in the present invention.

[0120] In the above general formula (6), p, q and r each independently represent the degree of polymerization of each monomer unit. The values ​​of s and t are related to the molecular weight, etc. s / (s+t) is preferably 0.01 to 0.99, more preferably 0.1 to 0.9. t / (s+t) is preferably 0.01 to 0.99, more preferably 0.1 to 0.9.

[0121] In the present embodiment, as the content of the diblock copolymer, there is no particular limitation and can be appropriately selected according to the purpose. As the present embodiment, relative to 100 parts by mass of the triblock copolymer, preferably 0 to 100 parts by mass of the diblock copolymer is contained, more preferably 1 to 50 parts by mass, and further preferably 10 to 50 parts by mass. If the content range of the tackifying resin in the adhesive layer is the above range, it is easy to ensure the adhesion with the adherend.

[0122] In the present embodiment, the weight average molecular weight Mw of the acrylic block copolymer is preferably 50,000 to 300,000, and the number average molecular weight Mn is 50,000 to 300,000. More preferably, the weight average molecular weight Mw of the block copolymer is 100,000 to 250,000, and the number average molecular weight Mn is 100,000 to 250,000, and the weight average molecular weight Mw of the block copolymer is further preferably 130,000 to 230,000, and the number average molecular weight Mn is 130,000 to 230,000. The preferred ranges of the weight average molecular weight Mw and the number average molecular weight Mn of the triblock copolymer represented by the general formula (1) are also the same as the above ranges.

[0123] When the weight average molecular weight Mw of the acrylic block copolymer is within the above range, it is preferred from the viewpoint of removability. When the number average molecular weight Mn of the acrylic block copolymer is within the above range, it is preferred from the viewpoint of removability.

[0124] Here, the weight average molecular weight M of the acrylic block polymer and the triblock copolymer represented by the general formula (1) determined by the GPC method is: W and number average molecular weight M N The measurement of is a standard polystyrene conversion value measured using a GPC apparatus (HLC-8329GPC, manufactured by Tosoh Corporation), and the measurement conditions are as follows. [Measurement conditions] Sample concentration: 0.5 mass% (tetrahydrofuran (THF) solution) Sample injection volume: 100μL Eluent: THF Flow rate: 1.0mL / min ·Measurement temperature: 40℃ Main column: TSKgel GMHHR-H (20) 2 pieces Guard column: TSKgel HXL-H Detector: Differential refractometer · Standard polystyrene molecular weight: 10,000 to 20,000,000 (manufactured by Tosoh Corporation) <Stereoregularity> The triblock copolymer represented by the general formula (1) of the present invention and / or a partial structure (e.g., block) of the triblock copolymer represented by the general formula (1) preferably has stereoregularity (stereoregularity). Specifically, the triblock copolymer of the present invention and / or a partial structure (e.g., block) of the triblock copolymer may have any stereoregularity of isotactic, syndiotactic, and atactic, or may have a plurality of blocks having any of these stereoregularities.

[0125] As a preferred embodiment of the triblock copolymer in the present invention, it is preferred that "-(A)" in the general formula (1) p The syndiotacticity of the polymer block of the -" portion shows a ratio of rr triads of 65% or more, and more preferably a ratio of rr triads of 75 to 95%. As a preferred embodiment of the triblock copolymer in the present invention, it is preferred that "-(C) r The syndiotacticity of the polymer block of the -" portion shows a ratio of rr triads of 65% or more, and more preferably a ratio of rr triads of 75 to 95%. As a preferred embodiment of the triblock copolymer in the present invention, "-(B)" in the general formula (1) r The polymer block containing the "-" portion preferably exhibits atactic structure.

[0126] The triblock copolymer of the present invention has a ratio of rr triads of 65% or more. p In the case of a polymer block having a "-" portion, the effects of good removability and high temperature holding power can be achieved.

[0127] Generally, the syndiotacticity of a polymer is expressed by the ratio of chains (triads) composed of three monomer units to rr. In this specification, it is calculated by NMR measurement of the polymer. Specifically, 13 The signal peaks representing the arrangement of triads in C-NMR vary depending on the type of polymer, measurement solvent, or measurement temperature, so the signals need to be identified and quantified according to the respective measurement conditions. It should be noted that in this specification, the samples dissolved in deuterated chloroform were measured at 50°C.

[0128] Preferred embodiments of the triblock copolymer in the present invention include polymethyl methacrylate block-polyn-butyl acrylate block-polymethyl methacrylate, polyethyl methacrylate block-polyn-butyl acrylate block-polyethyl methacrylate, polypropyl methacrylate block-polyn-butyl acrylate block-polypropyl methacrylate, polymethyl methacrylate block-polyt-butyl acrylate block-polymethyl methacrylate, and polymethyl methacrylate block-polypropyl acrylate block-polymethyl methacrylate.

[0129] The triblock copolymer in the present invention has a molecular weight distribution of the entire triblock copolymer represented by a ratio of weight average molecular weight / number average molecular weight, and is preferably in the range of 0.8 to 2.3, and more preferably in the range of 1.00 to 1.50.

[0130] From the viewpoint of adhesive properties, the "-(A)" contained in the molecule of the triblock copolymer of the present invention is p -" polymer block and "-(A) r The total weight of the polymer block of the "-" portion is equal to the total weight of the polymer block of the "-(B)" portion. q The ratio of the total weight of the polymer block of the -" portion is represented by the mass ratio of a / b, and is preferably in the range of 5 / 95 to 80 / 20, and more preferably in the range of 10 / 90 to 75 / 25.

[0131] In this embodiment, when A and C in the general formula (1) are different repeating units, from the viewpoint of adhesive properties, "-(A)" contained in the molecule of the triblock copolymer of the present invention is p -" (the total weight of the polymer block p The total weight of the polymer block of the "-" part is called a.) and "-(B) q -" (the total weight of the polymer block of the "- (B) q The total weight of the polymer block of the "-" portion is referred to as b. The ratio is represented by the mass ratio of a / b, which is preferably in the range of 2 / 98 to 67 / 33, and more preferably in the range of 5 / 95 to 60 / 40.

[0132] In this embodiment, when A and C in the general formula (1) are different repeating units, from the viewpoint of adhesive properties, the "-(C)" contained in the molecule of the triblock copolymer of the present invention is r -" (the total weight of the polymer block of the "- (C) p The total weight of the polymer block of the "-" part is called C.) and "-(B) q The ratio of the total weight of the polymer block of the -" portion is expressed as a mass ratio of c / b and is preferably in the range of 2 / 98 to 67 / 33, and more preferably in the range of 5 / 95 to 60 / 40.

[0133] In this embodiment, when A and C in the general formula (1) are the same repeating units, from the viewpoint of adhesive properties, "-(A)" contained in the molecule of the triblock copolymer of the present invention is p -" polymer block and "-(C) r -" (replace "-(A) p -" polymer block and "-(C) r The total weight of the polymer block of the "-" part is called d.) and "-(B) q The ratio of the total weight of the polymer block of the -" portion (referred to as b) is expressed as a mass ratio of d / b and is preferably in the range of 5 / 95 to 80 / 20, more preferably in the range of 10 / 90 to 75 / 25.

[0134] The triblock copolymer of the present invention may be modified with functional groups such as hydroxyl, carboxyl, anhydride, amino, trimethoxysilyl, etc. in the molecular side chain or at the molecular main chain terminal as needed within the range not impairing the effects of the present invention.

[0135] The method for producing the triblock copolymer used in the present embodiment is not particularly limited and can be appropriately selected from conventionally known production methods, such as a method in which block copolymers are sequentially polymerized by anionic living polymerization or cationic living polymerization. In addition, when the triblock copolymer used in the present embodiment has stereoregularity (e.g., syndiotacticity), a known method using an organic metal complex can be used.

[0136] As an example of a method for producing the triblock copolymer of the present invention, the triblock copolymer can be produced by the following method: in an inert polymerization solvent, using a polymerization initiator, polymerization of an alkyl methacrylate monomer as a main component, polymerization of an alkyl acrylate monomer as a main component and / or polymerization of a monomer having an alkyl methacrylate monomer as a main component are sequentially carried out in a manner to obtain a desired block connection order.

[0137] As a more specific method for producing the triblock copolymer, an anionic living polymerization method is firstly used to polymerize an alkyl methacrylate monomer in a polymerization solvent using a polymerization initiator to form a polyalkyl methacrylate block having a living terminal (corresponding to "-(A)" in the general formula (1)) having a living polymerizable end. p -" part). Second, starting from the active terminal of the polyalkyl methacrylate, an alkyl acrylate monomer is polymerized to obtain an alkyl methacrylate-alkyl acrylate binary block copolymer having an active terminal of the polyalkyl methacrylate (corresponding to "-(A)" in the general formula (1) p -(B) q-" part). Third, a part of the alkyl methacrylate-alkyl acrylate binary block copolymer having a living polymerizable active terminal is reacted with a coupling agent to form a coupled alkyl methacrylate-alkyl acrylate-alkyl methacrylate triblock copolymer (corresponding to "-(A)" in the general formula (1) p -(B) q -(C) r -" part). At this time, the polymerization is terminated by reacting with a polymerization terminator such as alcohol, if necessary.

[0138] Examples of the polymerization initiator include organic metal compounds such as organic lithium compounds and organic metal complexes.

[0139] As the organic metal complex, there can be mentioned rare earth metal complexes having pentamethylcyclopentadienyl as a ligand, such as samarium bis(pentamethylcyclopentadienyl)methyltetrahydrofuran, yttrium bis(pentamethylcyclopentadienyl)methyltetrahydrofuran, etc. In addition, these organic metal complexes can also be used in combination with alkyl aluminums such as trimethylaluminum.

[0140] Examples of the organic lithium compound include alkyl lithiums such as tert-butyl lithium, compounds obtained by reacting alkyl lithiums with 1,1-diphenylethylene, diphenylmethane, etc. In addition, these organic lithium compounds may be used in combination with inorganic salts such as lithium chloride, lithium salts of alkoxides such as 2-(2-methoxyethoxy)ethoxylithium, and organic aluminum compounds such as diisobutyl (2,6-di-tert-butyl-4-methylphenoxy)aluminum.

[0141] As the polymerization solvent, hydrocarbon solvents such as benzene, toluene, and xylene; halogenated hydrocarbon solvents such as chloroform, dichloromethane, and carbon tetrachloride; and ether solvents such as tetrahydrofuran and diethyl ether can be used.

[0142] The acrylic binder resin containing the acrylic block copolymer preferably accounts for 30 to 100% by mass, more preferably 50 to 95% by mass, of the entire binder resin used in the adhesive layer of the present invention.

[0143] The main component of the adhesive resin used in the adhesive layer of the present invention preferably includes an acrylic block copolymer, and more preferably includes a triblock copolymer represented by the general formula (1). The acrylic adhesive resin other than the triblock copolymer represented by the general formula (1) is not particularly limited, and may include the following acrylic adhesive resins, or the following rubber adhesive resins.

[0144] The acrylic binder resin other than the acrylic triblock copolymer is not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include resins containing an acrylic polymer and, if necessary, additives such as a tackifier resin and a crosslinking agent.

[0145] The acrylic polymer has a chemical structure other than the triblock copolymer represented by the general formula (1) and can be produced, for example, by polymerizing a (meth)acrylic acid ester monomer. As the (meth)acrylic acid ester monomer, for example, an alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms, etc. can be used.

[0146] Specific examples of the alkyl (meth)acrylate having an alkyl group with 1 to 12 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0147] As the alkyl (meth)acrylate having an alkyl group with 1 to 12 carbon atoms, an alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms is preferably used, and an alkyl (meth)acrylate having an alkyl group with 4 to 8 carbon atoms is more preferably used; from the perspective of ensuring excellent adhesion to the adherend, n-butyl acrylate is particularly preferably used.

[0148] The (meth)acrylic acid alkyl ester having an alkyl group having 1 to 12 carbon atoms is used preferably in the range of 0 to 50% by mass, more preferably in the range of 0 to 30% by mass, based on the total amount of monomers used in the production of the acrylic polymer.

[0149] As the monomers that can be used for producing the acrylic polymer, in addition to the above-mentioned monomers, a high-polarity vinyl monomer can be used as necessary.

[0150] Examples of the highly polar vinyl monomer include (meth)acrylic monomers having a hydroxyl group, (meth)acrylic monomers having a carboxyl group, (meth)acrylic monomers having an amide group, and the like, and sulfonic acid group-containing monomers such as vinyl acetate, ethylene oxide-modified succinic acid acrylate, and 2-acrylamide-2-methylpropanesulfonic acid. These monomers may be used alone or in combination of two or more.

[0151] Specific examples of the vinyl monomer having a hydroxyl group include (meth)acrylic monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate.

[0152] The vinyl monomer having a hydroxyl group is preferably used when a resin containing an isocyanate crosslinking agent is used as the binder resin. Specifically, as the vinyl monomer having a hydroxyl group, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate are preferably used.

[0153] The vinyl monomer having a hydroxyl group is used in an amount of preferably 0.01 to 1.0% by mass, more preferably 0.03 to 0.3% by mass, based on the total amount of monomers used for producing the acrylic polymer.

[0154] Specific examples of the vinyl monomer having a carboxyl group include (meth)acrylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, (meth)acrylic acid dimer, crotonic acid, and ethylene oxide-modified succinic acid acrylate. Among them, acrylic acid is preferred.

[0155] Specific examples of the vinyl group having an amide group include (meth)acrylic monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, acrylamide, and N,N-dimethylacrylamide.

[0156] The high polarity vinyl monomer is preferably used in the range of 1.5 to 20% by mass, more preferably in the range of 1.5 to 10% by mass, relative to the total amount of monomers used in the production of the acrylic polymer; when used in the range of 2 to 8% by mass, an adhesive layer with a balance in cohesion, retention and adhesion can be formed, which is further preferred.

[0157] The method for producing the acrylic polymer is not particularly limited and can be appropriately selected from known methods according to the purpose, and examples thereof include methods of polymerizing monomers by polymerization methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. Among them, the acrylic polymer is preferably produced by solution polymerization or bulk polymerization.

[0158] During the polymerization, as required, peroxide-based thermal polymerization initiators such as benzoyl peroxide and lauroyl peroxide; azo thermal polymerization initiators such as azobisisobutyronitrile; acetophenone-based photopolymerization initiators; benzoin ether-based photopolymerization initiators; benzyl ketal-based photopolymerization initiators; acylphosphine oxide-based photopolymerization initiators; benzoin-based photopolymerization initiators; benzophenone-based photopolymerization initiators, etc. can be used.

[0159] Regarding the weight average molecular weight of the acrylic polymer obtained by the above method, it is preferred to use an acrylic polymer having a weight average molecular weight of 300,000 to 3,000,000 measured in terms of standard polystyrene using gel permeation chromatography (GPC) in the same method and conditions as for the triblock copolymer, and it is more preferred to use an acrylic polymer having a weight average molecular weight of 500,000 to 2,500,000.

[0160] The acrylic binder resin other than the acrylic triblock copolymer preferably accounts for 0 to 40% by mass, more preferably 0 to 1% by mass, of the entire binder resin used in the adhesive layer of the present invention.

[0161] In the adhesive layer of the present invention, when the content of the acrylic binder resin other than the acrylic triblock copolymer is within the above range, initial adhesiveness can be easily improved while maintaining removability and high load holding power.

[0162] The rubber-based binder resin is not particularly limited, and examples thereof include resins containing a rubber material generally used as a binder resin, such as a synthetic rubber-based binder resin and a natural rubber-based binder resin, and, if necessary, an additive such as a tackifier resin.

[0163] As the rubber material, for example, block copolymers of aromatic vinyl compounds and conjugated diene compounds can be cited, specifically, styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, styrene-isoprene-butadiene-styrene copolymers, styrene-butadiene-styrene copolymers, styrene-ethylene-butylene copolymers, styrene-ethylene-propylene copolymers and their hydrides and the like can be cited. They can be used alone or in combination of two or more. Among them, the combination of two or more styrene resins can give excellent adhesive properties and holding power to the adhesive tape, so it is more preferred; particularly preferably, the combination of styrene-isoprene copolymers and styrene-isoprene-styrene copolymers is used.

[0164] Styrene resins can be used, for example, styrene resins of a single structure of a linear structure, a branched structure or a multi-branched structure, or styrene resins of different structures can be mixed and used. When a styrene resin rich in a linear structure is used for an adhesive layer, excellent bonding properties can be imparted to the adhesive tape. On the other hand, although a branched structure or a multi-branched structure is provided with a styrene block at the molecular end, a pseudo cross-linked structure can be adopted, which can impart excellent cohesive force, and thus can impart high holding power. Therefore, styrene resins are preferably used in a mixed manner according to the characteristics required.

[0165] As the styrene resin, it is preferred to use a styrene resin having a structural unit represented by the following chemical formula (B) in a range of 10 to 80% by mass, more preferably a styrene resin having a structural unit represented by the following chemical formula (B) in a range of 12 to 60% by mass, further preferably a styrene resin having a structural unit represented by the following chemical formula (B) in a range of 15 to 40% by mass, and particularly preferably a styrene resin having a structural unit represented by the following chemical formula (B) in a range of 17 to 35% by mass, relative to the total mass of the styrene resin. Thus, excellent adhesiveness and heat resistance can be obtained. [Chemistry 9] The rubber-based binder resin preferably accounts for 0 to 50% by mass, and more preferably accounts for 0 to 30% by mass, based on the entire binder resin used in the adhesive layer of the present invention.

[0166] In the adhesive layer of the present invention, when the content of the rubber-based binder resin is within the above range, it is easy to achieve both adhesiveness, disassembly properties, and high load holding power.

[0167] <<Aromatic vinyl binder resin containing styrene block copolymer>> The aromatic vinyl binder resin containing a styrene block copolymer preferably used as the main component of the binder resin is not particularly limited, and examples thereof include resins containing rubber materials commonly used as binder resins such as synthetic rubber binder resins and natural rubber binder resins, and additives such as tackifying resins as required.

[0168] Aromatic vinyl adhesive resins other than styrene block copolymers, for example, preferably contain block copolymers of monovinyl-substituted aromatic compounds and conjugated diene compounds as base polymers. The monovinyl-substituted aromatic compound refers to a compound having a functional group having a vinyl group bonded to an aromatic ring. As a representative example of the aromatic ring, a benzene ring (which may be a benzene ring substituted by a functional group (such as an alkyl group) not having a vinyl group) can be cited. As a specific example of the monovinyl-substituted aromatic compound, styrene, α-methylstyrene, vinyltoluene, vinylxylene, etc. can be cited. As a specific example of the conjugated diene compound, 1,3-butadiene, isoprene, etc. can be cited. Such a block copolymer can be used alone or in combination of two or more as a base polymer.

[0169] For the A segment (hard segment) in the block copolymer, the copolymerization ratio of the monovinyl-substituted aromatic compound (two or more kinds may be used in combination) is preferably 70% by mass or more (more preferably 90% by mass or more, and substantially 100% by mass). For the B segment (soft segment) in the block copolymer, the copolymerization ratio of the conjugated diene compound (two or more kinds may be used in combination) is preferably 70% by mass or more (more preferably 90% by mass or more, and substantially 100% by mass). Such a block copolymer can achieve a higher performance adhesive tape.

[0170] The block copolymer can be a diblock, a triblock, a radial, a mixture thereof, and the like. In triblocks and radials, it is preferred that an A segment (such as a styrene block) is disposed at the end of the polymer chain. This is because the A segment disposed at the end of the polymer chain is easily aggregated to form a microdomain, thereby forming a pseudo cross-linked structure, and the cohesion of the adhesive is improved. As a block copolymer in the technology disclosed herein, from the viewpoint of the adhesive force (peel strength) and rebound resistance to the adherend, for example, a diblock ratio of 30% by mass or more (more preferably 40% by mass or more, more preferably 50% by mass or more, particularly preferably 60% by mass or more, typically 65% ​​by mass or more, for example 70% by mass or more) can be preferably used. In addition, from the viewpoint of the resistance to the stress continuously applied, a diblock ratio of 90% by mass or less (more preferably 85% by mass or less, for example 80% by mass or less) is preferably used. For example, a block copolymer having a diblock content of 60 to 85% by mass is preferably used.

[0171] In the styrene block copolymer of the present invention, the base polymer is a styrene block copolymer. For example, it can be preferably implemented in a manner that the base polymer includes at least one of a styrene isoprene block copolymer and a styrene butadiene block copolymer. In the styrene block copolymer contained in the binder resin, it is preferred that the ratio of styrene isoprene block copolymer is more than 70% by mass, or the ratio of styrene butadiene block copolymer is more than 70% by mass, or the total ratio of styrene isoprene block copolymer and styrene butadiene block copolymer is more than 70% by mass. In a preferred embodiment, substantially all (e.g., 95 to 100% by mass) of the styrene block copolymer is a styrene isoprene block copolymer. In another preferred embodiment, substantially all (e.g., 95 to 100% by mass) of the styrene block copolymer is a styrene butadiene block copolymer. According to such a composition, an adhesive tape having excellent rebound resistance and good balance with other adhesive properties can be suitably achieved.

[0172] The styrene block copolymer can be in the form of a diblock, a triblock, a radial, or a mixture thereof. In triblocks and radials, a styrene block is preferably disposed at the end of the polymer chain. This is because the styrene blocks disposed at the ends of the polymer chains are easily aggregated to form styrene microdomains, thereby forming a pseudo cross-linked structure, and the cohesion of the adhesive is improved. As the styrene block copolymer used in the technology disclosed herein, from the viewpoint of the adhesion (peel strength) and rebound resistance to the adherend, for example, a styrene block copolymer having a diblock ratio of 30% by mass or more (more preferably 40% by mass or more, further preferably 50% by mass or more, particularly preferably 60% by mass or more, typically 65% ​​by mass or more) can be preferably used. It can also be a styrene block copolymer having a diblock ratio of 70% by mass or more (for example, 75% by mass or more). In addition, from the viewpoints of holding power, a styrene block copolymer having a diblock ratio of 90% by mass or less (more preferably 85% by mass or less, for example, 80% by mass or less) can be preferably used. For example, a styrene-based block copolymer having a diblock ratio of 60 to 85% by mass can be preferably used.

[0173] The styrene content of the styrene block copolymer can be, for example, 5 to 40% by mass. From the viewpoint of rebound resistance and holding power, a styrene block copolymer having a styrene content of 10% by mass or more (more preferably greater than 10% by mass, for example, 12% by mass or more) is generally preferred. In addition, from the viewpoint of adhesion to an adherend, a styrene block copolymer having a styrene content of 35% by mass or less (typically less than 30% by mass, more preferably less than 25% by mass, for example, less than 20% by mass) is preferred. For example, a styrene block copolymer having a styrene content of 12% by mass or more and less than 20% by mass can be preferably used.

[0174] The aromatic vinyl binder resin containing the styrene block copolymer preferably accounts for 50 to 100% by mass of the entire binder resin used in the adhesive layer of the present invention, and more preferably accounts for 50 to 100% by mass of the aromatic vinyl binder resin containing the styrene block copolymer.

[0175] In the adhesive layer of the present invention, if the content of the aromatic vinyl adhesive resin containing the styrene block copolymer is 50% by mass or more, it is easy to maintain removability and high load holding power. On the other hand, if the content of the acrylic adhesive resin containing the acrylic block copolymer is 50% by mass or more, it is easy to maintain removability and high load holding power.

[0176] The main component of the binder resin used in the adhesive layer of the present invention preferably includes a styrene block copolymer. The aromatic vinyl binder resin other than the styrene block copolymer is not particularly limited and may include the above-mentioned acrylic binder resin or the above-mentioned rubber binder resin.

[0177] <<Tackifying resin>> The adhesive layer of the present embodiment contains a tackifier resin. The tackifier resin is preferably used to improve the adhesion to the adherend and the surface adhesive strength.

[0178] The tackifier resin of the present embodiment preferably has a softening point of 95°C or higher. A more preferred softening point is 95°C to 180°C; from the perspective of forming an adhesive layer with high adhesive performance, a more preferred softening point is 95°C to 140°C. It should be noted that when a (meth)acrylate-based tackifier resin is used, its glass transition temperature is preferably 30°C to 200°C, and more preferably 50°C to 160°C.

[0179] As the specific example of the tackifying resin, rosin-based tackifying resin, polymerized rosin-based tackifying resin, polymerized rosin ester-based tackifying resin, rosin phenol-based tackifying resin, stabilized rosin ester-based tackifying resin, disproportionated rosin ester-based tackifying resin, hydrogenated rosin ester-based tackifying resin, terpene-based tackifying resin, terpene-phenol-based tackifying resin, petroleum resin-based tackifying resin, (methyl) acrylate-based tackifying resin, etc. can be enumerated. They can be used alone or in combination of more than two kinds. Among them, the preferred polymerized rosin ester-based tackifying resin of the tackifying resin is rosin phenol-based tackifying resin, disproportionated rosin ester-based tackifying resin, hydrogenated rosin ester-based tackifying resin, terpene-phenol-based resin, (methyl) acrylate-based resin.

[0180] Specific examples of the rosin-based tackifying resin include unmodified rosins (crude rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins obtained by modifying these unmodified rosins by hydrogenation, disproportionation, polymerization, etc. (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc., the same below); and various other rosin derivatives. Examples of the rosin derivatives include rosin esters such as those obtained by esterifying unmodified rosin with alcohols (i.e., esters of rosin) and those obtained by esterifying modified rosin with alcohols (i.e., esters of modified rosin); unsaturated fatty acid-modified rosins obtained by modifying unmodified rosin or modified rosin with unsaturated fatty acids; unsaturated fatty acid-modified rosin esters obtained by modifying rosin esters with unsaturated fatty acids; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin, unsaturated fatty acid-modified rosin or unsaturated fatty acid-modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; rosin phenol resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and thermally polymerizing them; and the like. When an acrylic polymer is used as the base polymer, a rosin-based tackifier resin is preferably used. From the viewpoint of improving adhesive properties such as adhesion, it is more preferred to use two or more rosin-based tackifier resins in combination with different types and properties (such as softening points).

[0181] Examples of the terpene-based tackifying resin include terpene resins such as α-pinene polymers, β-pinene polymers, and dipentene polymers; modified terpene resins obtained by modifying these terpene resins (phenol modification, aromatic modification, hydrogenation modification, hydrocarbon modification, etc.). Examples of the modified terpene resins include terpene-modified phenolic resins, styrene-modified terpene resins, aromatic-modified terpene resins, hydrogenated terpene resins, etc. When an acrylic polymer is used as the base polymer, it is preferred to use a terpene-based tackifying resin (such as a terpene-modified phenolic resin). In particular, from the viewpoint of improving adhesive properties such as adhesion, it is preferred to use one or more of the terpene-based tackifying resins (such as terpene-modified phenolic resins) in combination with different types and properties (such as softening points).

[0182] Examples of hydrocarbon-based tackifying resins include various hydrocarbon-based resins such as aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone indene resins.

[0183] As the tackifying resin, a tackifying resin having a softening point (softening temperature) of 95°C or more can be preferably used. By using an adhesive containing a tackifying resin having a softening point above the above lower limit, an adhesive tape with better adhesion can be achieved. Among the tackifying resins exemplified above, a terpene-based tackifying resin (e.g., terpene-modified phenolic resin), a rosin-based tackifying resin (e.g., an ester of polymerized rosin), etc. having the above softening point can be preferably used. There is no particular restriction on the upper limit of the softening point of the tackifying resin, and for example, it can be set to about 200°C or less. It should be noted that the softening point of the tackifying resin described herein is defined as a value measured by the softening point test method (ring and ball method) specified in either JIS K 5902 or JIS K 2207.

[0184] The amount of the tackifier resin used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 5 to 65 parts by mass relative to 100 parts by mass of the adhesive resin. When used in the range of 8 to 55 parts by mass, it is easy to ensure adhesion to the adherend, so it is more preferred.

[0185] As the binder resin containing an acrylic block copolymer or a styrene block copolymer in the present embodiment, it is preferable to use a binder resin containing a crosslinking agent in order to further improve the cohesive force of the adhesive layer.

[0186] The crosslinking agent is not particularly limited and can be appropriately selected according to the purpose, for example, isocyanate crosslinking agents, epoxy crosslinking agents, metal chelate crosslinking agents, aziridine crosslinking agents, etc. can be used alone or in combination of two or more. Among them, the crosslinking agent is preferably a crosslinking agent of the type that is mixed after the manufacture of the acrylic acid polymer to allow the crosslinking reaction to proceed, and more preferably an isocyanate crosslinking agent and an epoxy crosslinking agent that are highly reactive with the acrylic acid polymer are used.

[0187] As the isocyanate crosslinking agent, for example, toluene diisocyanate, triphenylmethane isocyanate, naphthalene-1,5-diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, trimethylolpropane-modified toluene diisocyanate, etc. can be mentioned. These can be used alone or in combination of two or more. Among them, toluene diisocyanate, which is a trifunctional polyisocyanate compound, and its trimethylolpropane adducts and triphenylmethane isocyanate are particularly preferred.

[0188] In this specification, as an index of the degree of crosslinking, the insoluble components are measured after the adhesive layer is immersed in toluene for 24 hours, and the gel fraction obtained is used. The gel fraction of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 10 to 70% by mass, more preferably 25 to 65% by mass; from the perspective of obtaining an adhesive layer with good cohesiveness and adhesion, it is further preferably 35 to 60% by mass.

[0189] It should be noted that the gel fraction refers to a value measured by the following method. An adhesive composition containing an adhesive resin and further additives as required is applied to a release sheet in such a manner that the thickness after drying becomes 50 μm, dried at 100°C for 3 minutes, aged at 40°C for 2 days, and the resultant is cut into 50 mm squares to serve as a sample. Next, the mass (G1) of the sample before immersion in toluene is measured in advance, and the toluene-insoluble components of the sample after immersion in a toluene solution at 23°C for 24 hours are separated by filtering with a 300-mesh metal mesh, and the mass (G2) of the residue after drying at 110°C for 1 hour is measured, and the gel fraction is calculated according to the following mathematical formula (4). It should be noted that the mass (G3) of the conductive particles in the sample is calculated from the mass (G1) of the sample and the composition of the adhesive composition.

[0190] Gel fraction (mass %) = (G2-G3) / (G1-G3) × 100 Mathematical formula (4) As other components in the adhesive layer of the present embodiment, there is no particular limitation, and they can be appropriately selected within the range that does not damage the characteristics of the adhesive tape, for example, polymer components other than the adhesive resin, crosslinking agents, anti-aging agents, ultraviolet absorbers, fillers, polymerization inhibitors, surface regulators, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, plasticizers, softeners, flame retardants, metal deactivators, silica beads, organic beads and other additives; inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, antimony pentoxide, etc. They can be used alone or in combination of two or more.

[0191] The content of other components in the adhesive layer of the present embodiment can be appropriately selected within a range that does not impair the properties of the adhesive tape.

[0192] <Packing> The adhesive layer of the adhesive tape of the present embodiment preferably contains a filler, a tackifier resin, and a binder resin.

[0193] In the present embodiment, the adhesive composition as the precursor of the adhesive layer preferably contains filler.By making the adhesive composition as the precursor of the adhesive layer include this filler, the filler can be exposed from this adhesive layer when the adhesive tape is elongated, so that the bonding area of ​​the adhesive layer and the adherend decreases.Therefore, even in the case of a larger angle, such as a vertical direction (also referred to as "90 ° direction") relative to the attachment surface (hereinafter, sometimes referred to as "adhesive surface") of the adhesive tape in the elongation direction of the adhesive tape, in addition, even in the case of stretching at a fast speed, it is also possible to more simply and more quickly peel off the adhesive tape.

[0194] The type of the filler is not particularly limited and can be appropriately selected within a range that does not impair the effects of the present invention, and may be an inorganic filler or an organic filler. These may be used alone or in combination of two or more.

[0195] Specific examples of the inorganic filler include aluminum hydroxide, magnesium hydroxide, aluminum oxide, silicon oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, iron oxide, silicon carbide, boron nitride, aluminum nitride, titanium nitride, silicon nitride, titanium boride, carbon, nickel, copper, aluminum, titanium, gold, silver, zirconium hydroxide, basic magnesium carbonate, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, tin oxide, tin oxide hydrate, borax, zinc borate, zinc metaborate, barium metaborate, zinc carbonate, magnesium-calcium carbonate, calcium carbonate, barium carbonate, molybdenum oxide, antimony oxide. , red phosphorus, mica, clay, kaolin, talc, zeolite, wollastonite, montmorillonite, silica (quartz, fumed silica, precipitated silica, anhydrous silicic acid, fused silica, crystalline silica, ultrafine amorphous silica, etc.), potassium titanate, magnesium sulfate, sepiolite, vermiculite, aluminum borate, barium sulfate, barium titanate, zirconium oxide, cerium, tin, indium, carbon, sulfur, tellurium (Japanese: テリウム), cobalt, molybdenum, strontium, chromium, barium, lead, tin oxide, indium oxide, diamond, magnesium, platinum, zinc, manganese, stainless steel, etc. Among them, aluminum hydroxide, nickel, etc. are preferred.

[0196] Furthermore, the inorganic filler may be one that has been surface-treated by silane coupling treatment, stearic acid treatment, or the like in order to improve dispersibility in the binder resin.

[0197] Specific examples of the organic filler include polystyrene fillers, benzoguanamine fillers, polyethylene fillers, polypropylene fillers, silicone fillers, urea-formalin fillers, styrene / methacrylic acid copolymers, fluorine fillers, acrylic fillers, polycarbonate fillers, polyurethane fillers, polyamide fillers, epoxy resin fillers, thermosetting resin hollow fillers, etc.

[0198] It should be noted that, among the organic fillers, as the organosilicon-based filler, specifically, organosilicon rubber particles obtained by three-dimensionally crosslinking straight-chain organopolysiloxane (refer to Japanese Patent Publication No. 63-77942, Japanese Patent Publication No. 3-93834, Japanese Patent Publication No. 04-198324), powdered organosilicon rubber (refer to U.S. Patent No. 3843601, Japanese Patent Publication No. 62-270660, Japanese Patent Publication No. 59-96122), etc. can be used. In addition, organosilicon composite particles having a structure in which the surface of the organosilicon rubber particles obtained by the above method is coated with an organosilicon resin as a cured polyorganosilsesquioxane having (R′SiO 3 / 2 ) n (R' represents a substituted or unsubstituted monovalent hydrocarbon group) is a structure represented by cross-linking into a three-dimensional network (see Japanese Patent Application Laid-Open No. 7-196815).

[0199] As the silicone particles, there can be used silicone particles commercially available under the above-mentioned trade names such as TREFIL E-500, TREFIL E-600, TREFIL E-601, and TREFIL E-850 from Dow Corning Toray Silicone Co., Ltd., and silicone particles commercially available under the above-mentioned trade names such as KMP-600, KMP-601, KMP-602, and KMP-605 from Shin-Etsu Chemical Co., Ltd.

[0200] In addition, acrylic modified silicone particles can be used as other silicone fillers. Examples of acrylic modified silicone particles include emulsified graft polymers of polyorganosiloxane represented by the following general formula (C), acrylic ester monomers and / or methacrylic ester monomers, and monomers containing functional groups copolymerizable therewith. [Chemistry 10] (In the above general formula (C), R 5 and R 6 Each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and X 1 , X 2 , X 3 , X 4 , X 5 and X 6 each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group, and Y 1 and Y 2 Each independently represents X1 or -[O-Si(X 7 )(X 8 )] c -X 9 The group shown, X 7 , X 8 and X 9 Each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group, and X 1 , X 2 , X 3 , X 4 , X 5 , X 6 , X 7 , X 8 and X 9 and Y 1 and Y 2 At least two of the groups are hydroxyl groups, and a, b and c are each independently a positive number satisfying 0≤a≤1000, 100≤b≤10000, and 1≤c≤1000. ) In the general formula (C), R 5 or R 6 The alkyl group having 1 to 20 carbon atoms shown may be straight-chain, branched, or cyclic. Specifically, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, hexadecyl, octadecyl, cyclopentyl, cyclohexyl, cycloheptyl, etc. may be mentioned. These alkyl groups may be substituted by halogen atoms, acryloyloxy, methacryloyloxy, carboxyl, alkoxy, alkenyloxy, amino, alkyl, alkoxy, or (meth)acryloyloxy substituted amino groups.

[0201] As R 5 or R 6 Examples of the aryl group having 6 to 20 carbon atoms include phenyl, tolyl, naphthyl and the like.

[0202] As R 5 or R 6 , preferably methyl.

[0203] In the general formula (C), X 1 ~X 9 The alkyl group having 1 to 20 carbon atoms and the aryl group having 6 to 20 carbon atoms represented by 5 or R 6 The alkyl group and the aryl group exemplified in are the same groups.

[0204] As X 1 ~X 9Examples of the alkoxy group having 1 to 20 carbon atoms include methoxy, ethoxy, propoxy, butoxy, hexyloxy, heptyloxy, octyloxy, decyloxy and tetradecyloxy.

[0205] In the general formula (C), a, b and c are positive numbers of 0≤a≤1000, 100≤b≤10000, and 1≤c≤1000, and a is preferably a positive number of 0 to 200. If a is greater than 1000, the strength of the obtained coating becomes insufficient. b is preferably a positive number of 1000 to 5000. If b is less than 100, the softness of the coating is insufficient, and if it is greater than 10000, it is difficult to form a solid shape such as particles. c is preferably a positive number of 1 to 200.

[0206] In addition, from the viewpoint of crosslinking properties, the polyorganosiloxane represented by the general formula (C) has at least 2, preferably 2 to 4, hydroxyl groups in one molecule, and preferably has the hydroxyl groups at both ends of the molecular chain.

[0207] Examples of the acrylic acid ester monomer or methacrylic acid ester monomer include methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, and cyclohexyl methacrylate.

[0208] Examples of the functional group-containing monomer copolymerizable with the acrylic acid ester monomer and / or the methacrylic acid ester monomer include monomers having an unsaturated bond including a carboxyl group, an amide group, a hydroxyl group, a vinyl group, an allyl group, and the like.

[0209] Preferably, 100 parts by mass of the polyorganosiloxane represented by the general formula (4) are mixed with 10 to 100 parts by mass of an acrylate monomer and / or a methacrylate monomer and 0.01 to 20 parts by mass of a monomer containing a functional group copolymerizable therewith, and emulsion graft polymerization is performed to obtain the acrylic modified silicone powder. The conditions in the emulsion graft polymerization are not particularly limited, and as the initiator used in the polymerization, a known free radical initiator commonly used for acrylic polymers can be used. In addition, the emulsifier can also use a known anionic surfactant or nonionic surfactant.

[0210] The acrylic modified silicone particles are granulated and powdered by the following methods. That is, spray drying, airflow drying, etc. are mentioned, but spray drying is preferred in view of productivity. The powder is preferably thermally dried, preferably at 80 to 150°C.

[0211] As the acrylic modified silicone particles, for example, commercially available products such as CHALINE R-170S and CHALINER-200 (both manufactured by Nissin Chemical Industry Co., Ltd.) may be used.

[0212] As the shape of the filler of the present embodiment, there is no particular restriction, can be suitably selected according to the purpose, can be a regular shape, can also be an irregular shape.As the specific example of the shape of the filler, polygonal, cubic, elliptical, spherical, needle-shaped, flat, flaky, etc. can be enumerated.The filler of these shapes can be used alone 1 kind, and can also be used in combination with more than 2 kinds.In addition, it can also be the material that the filler of these shapes cohesively forms.Wherein, as the shape of the filler, preferably elliptical, spherical, polygonal.If the filler shape is shapes such as elliptical, spherical, polygonal, then when the adhesive tape is extended, the sliding of the adhesive layer relative to the adherend becomes good, and the adhesive tape can be peeled off more simply and more quickly.

[0213] The particle size distribution (D90 / D10) of the filler of the present embodiment is not particularly limited and can be appropriately selected according to the purpose, preferably 2.5 to 20; from the perspective of impact resistance, it is more preferably 2.5 to 15, and further preferably 2.5 to 5. If the particle size distribution (D90 / D10) of the filler is within the preferred range, the adhesive tape can be peeled off more easily and quickly, and it is not easy to break even when the thickness of the substrate of the adhesive tape is thin, and the impact resistance, shear adhesion and cleavage adhesion are excellent. On the other hand, if the particle size distribution (D90 / D10) of the filler is less than 2.5, the elongation peelability is sometimes impaired, and if it exceeds 20, the bonding properties such as impact resistance, shear adhesion, and cleavage adhesion are sometimes impaired.

[0214] The particle size distribution (D90 / D10) of the filler in the present embodiment is obtained by measuring the average particle size of the filler using a measuring device (Microtrac) using a laser diffraction scattering method and converting the result into a particle size distribution, for example.

[0215] The average particle size of the filler of this embodiment is 0.1 to 40 μm, preferably 5 to 40 μm, more preferably 10 to 35 μm, further preferably 10 to 30 μm, and particularly preferably 10 to 25 μm. If the average particle size of the filler is within the preferred range, the adhesive tape can be peeled off more easily and quickly, and it is not easy to break even when the thickness of the substrate of the adhesive tape is thin, and the impact resistance, shear adhesion and cleavage adhesion are excellent. On the other hand, if the particle size of the filler is less than 0.1 μm, the elongation peelability may be impaired; if it exceeds 40 μm, the bonding properties such as impact resistance, shear adhesion and cleavage adhesion may be impaired.

[0216] In addition, the average particle size of the filler in the present embodiment refers to a volume average particle size, and can be measured by using, for example, a measuring device (Microtrac) using a laser diffraction scattering method.

[0217] It should be noted that, when the silicone rubber particles or silicone composite particles are used as fillers in the present embodiment, the average particle size of the silicone rubber particles or silicone composite particles is preferably 0.1 to 40 μm, and more preferably 5 to 40 μm. If the average particle size is less than 0.1 μm, the effect of reducing the bonding area caused by the filler when the adhesive tape is stretched tends to decrease; and if the average particle size is greater than 40 μm, the adhesive force of the adhesive tape tends to decrease.

[0218] In addition, when the acrylic modified silicone particles are used as the filler of the present embodiment, the average particle size of the acrylic modified silicone particles is preferably 0.1 to 40 μm, more preferably 5 to 40 μm, further preferably 5 to 30 μm, and further preferably 10 to 25 μm. If the average particle size is less than 0.1 μm, the effect of reducing the bonding area caused by the filler when the adhesive tape is extended tends to decrease; and if it is greater than 40 μm, the adhesive force of the adhesive tape tends to decrease.

[0219] As the ratio of the average particle size of the filler of the present embodiment to the average thickness of the adhesive layer, there is no particular restriction, and it can be appropriately selected according to the purpose, and the ratio of the average particle size of the filler represented by [volume average particle size of the filler / average thickness of the adhesive layer] to the average thickness of the adhesive layer is preferably 5 / 100 or more, more preferably 5 / 100 to 95 / 100, further preferably 10 / 100 to 75 / 100, and particularly preferably 20 / 100 to 60 / 100. If the ratio is more than 5 / 100, the adhesive tape can be peeled off more simply and more quickly, and it is not easy to break even when the thickness of the substrate of the adhesive tape is thin. In addition, from the aspect that the bonding performance such as impact resistance, shear bonding strength, and cleavage bonding strength is also more excellent, it is advantageous for the ratio to be less than 95 / 100.

[0220] The content of the filler in the adhesive layer of the present embodiment is preferably 0 to 300 mass %, more preferably 1 to 100 mass %, preferably 1 to 10 to 70 mass %, and more preferably 20 to 50 mass % relative to 100 mass % of the adhesive resin. By making the content of the filler relative to 100 mass % of the adhesive resin 1 mass % or more, the adhesive tape can be peeled off more simply and more quickly. In addition, by making the content of the filler relative to 100 mass % of the adhesive resin 50 mass % or less, it is possible to prevent the adhesive composition from remaining on the adherend, the impact resistance from deteriorating, or the shear bonding strength and the cleavage bonding strength from weakening.

[0221] The content of the filler in the adhesive layer of the present embodiment can be appropriately adjusted when preparing the adhesive composition as an adhesive layer precursor.

[0222] When the silicone rubber particles or silicone composite particles are used as fillers, the content of the silicone rubber particles or silicone composite particles is preferably 20 to 70% by mass based on 100% by mass of the adhesive layer.

[0223] When the acrylic modified silicone particles are used as a filler, the content of the acrylic modified silicone particles is preferably 20 to 70% by mass based on 100% by mass of the adhesive layer.

[0224] The volume ratio of the filler of this embodiment to the volume of the entire adhesive layer is preferably 4 to 40%, more preferably 5 to 30%, further preferably 5 to 20%, and most preferably 5 to 15%. By making the volume ratio of the filler 4% or more, the adhesive tape can be peeled off more simply and more quickly. In addition, by making the volume ratio of the filler 40% or less, it is possible to prevent the adhesive layer from remaining on the adherend, the impact resistance from being deteriorated, and the shear bonding strength and the cleavage bonding strength from being weakened.

[0225] The volume ratio of the filler to the adhesive layer can be calculated by the following mathematical formulas (1) to (3).

[0226] Binder resin* 1 Mass A(g) / Binder resin* 1 Density A(g / cm 3 ) = Volume A of binder resin*1 (cm 3 )···Mathematical formula (1) The mass of the filler is B (g) / the density of the filler is B (g / cm 3 ) = volume of filler B (cm 3 )···Mathematical formula (2) The volume of the packing B (cm 3 ) / (Binder resin* 1 Volume A(cm 3 ) + volume of filler B (cm 3 ))×100=volume ratio of filler (%)···Mathematical formula (3) It should be noted that in the above mathematical formulas (1) and (3), * 1 The binder resin shown may contain other components described below. The density is a value measured in accordance with JIS Z 8804.

[0227] The pressure-sensitive adhesive tape of the present embodiment may be provided with one or more other layers as appropriate according to the purpose. Examples of such other layers include a primer layer, an antistatic layer, a non-combustible layer, a decorative layer, a conductive layer, a thermal conductive layer, and a release layer.

[0228] The shape and size of the adhesive tape of this embodiment are not particularly limited as long as it has a base layer and an adhesive layer located on at least one surface of the base layer. For example, it includes an adhesive tape with a shape and size suitable for attachment to a specified adherend (for example, an adhesive tape in a state after punching), and a sheet-like long strip of adhesive tape (for example, an adhesive tape before being processed into a specific shape).

[0229] Furthermore, the pressure-sensitive adhesive tape of the present embodiment may be arbitrarily provided with a non-adhesive handle region, for example, in order to attach to or peel off an adherend.

[0230] The (average) thickness of the adhesive tape is not particularly limited and may be appropriately selected depending on the (average) thickness of the adhesive layer and the substrate layer, and is preferably 15 to 800 μm, more preferably 30 to 540 μm, further preferably 60 to 320 μm, and particularly preferably 70 to 250 μm.

[0231] It should be noted that, in this specification, "the thickness of the adhesive tape" means: the adhesive tape is cut into 5 places in the width direction at intervals of 100 mm in the length direction, and the thickness of the adhesive layer is measured at 5 places in the width direction at intervals of 100 mm in each cut surface using a TH-104 paper / film thickness measuring machine (manufactured by TESTER SANGYO Co., Ltd.), and the thickness of the total 25 places is averaged to obtain the average value. The hardness (A-type hardness (Shore A hardness)) of the adhesive tape is not particularly limited and can be appropriately selected according to the purpose, preferably 10 to 90, more preferably 20 to 85, and further preferably 64 to 85. If the Shore A hardness of the adhesive tape is within the preferred range, the re-peeling operation by stretching and peeling the adhesive tape becomes easy. On the other hand, if the Shore A hardness is less than 10, the adhesive tape may sometimes break when the adhesive tape is stretched and peeled off; if it exceeds 90, when the adhesive tape is stretched and peeled off, the stress used for stretching becomes too high, so that it is sometimes impossible to peel off again.

[0232] The rubber hardness of the adhesive tape is Shore A hardness, which refers to a value measured in accordance with JIS K 6253 using a durometer (spring type rubber durometer) (model: GS-719G, manufactured by TECLOCK Co., Ltd.). The 25% elongation stress of the adhesive tape is preferably 0.15MPa to 82MPa, more preferably 0.16 to 10MPa, further preferably 0.17 to 5MPa, and most preferably 0.18 to 4.5MPa. If the 25% elongation stress of the adhesive tape is 0.15MPa to 82MPa, a bonding strength suitable for the adhesive tape can be obtained, and it can be peeled off relatively easily even when the adhesive tape is elongated and peeled off. On the other hand, if the 25% elongation stress of the adhesive tape is lower than 0.15MPa, the adhesive tape may be peeled off when a load in the shear direction of the adhesive tape is generated while fixing the hard adherends to each other. In addition, if the 25% elongation stress of the adhesive tape exceeds 82MPa, when peeling the adhesive tape, there is a tendency that the force required to elongate the adhesive tape becomes too large.

[0233] The 25% elongation stress of the adhesive tape refers to the stress value measured when the adhesive tape is punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and stretched in the longitudinal direction at a tensile speed of 500 mm / min under the conditions of a measuring atmosphere of 23°C and 50% RH using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) to achieve an elongation of 25%.

[0234] The breaking stress of the adhesive tape is not particularly limited and can be appropriately selected according to the purpose, preferably 10 to 100.0 MPa, more preferably 15 to 90.0 MPa, further preferably 30 to 90.0 MPa, and particularly preferably 40 to 90.0 MPa. If the breaking stress of the adhesive tape is within the preferred range, the adhesive tape can be prevented from breaking even when the adhesive tape is rapidly stretched and peeled off, and the load used to elongate the adhesive tape will not become excessive, so the re-peeling operation performed by stretching and peeling becomes easy. On the other hand, if the breaking stress of the adhesive tape is less than 10 MPa, the adhesive tape sometimes breaks when the adhesive tape is rapidly stretched and peeled off; if it exceeds 100.0 MPa, when the adhesive tape is stretched and peeled off again, it is sometimes not fully stretched and cannot be peeled off. It should be noted that the force required to stretch the adhesive tape to deform it also depends on the thickness of the adhesive tape. For example, when the adhesive tape with a thick thickness and high breaking stress is stretched and peeled off again, it is sometimes not fully stretched and cannot be peeled off again.

[0235] The breaking stress of an adhesive tape is the stress value measured when the adhesive tape is punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0236] The elongation at break of the adhesive tape is not particularly limited and can be appropriately selected according to the purpose, preferably 400% to 2000%, more preferably 500% to 1800%, and further preferably 600% to 1200%. If the elongation at break of the adhesive tape is 400% or more, even when the adhesive tape is firmly bonded to the adherend, when the adhesive tape is peeled off again, the stress for stretching in the horizontal direction to the vertical direction relative to the adherend's attachment surface will not become too large, and even when the adhesive tape is stretched and peeled off, the adhesive tape will not be over-stretched and can be easily peeled off. In addition, if the elongation at break is 2000% or less, when the adhesive tape is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the adherend's attachment surface will not become too long, and the operation can be performed in a small space. On the other hand, if the elongation at break is less than 500%, when the adhesive tape is peeled off again, it may break when being stretched in the horizontal direction to the vertical direction relative to the attachment surface of the adherend and cannot be peeled off; if it exceeds 1300%, when the adhesive tape is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attachment surface of the adherend may become too long, thereby deteriorating the workability.

[0237] The breaking elongation of an adhesive tape is the tensile elongation measured when the adhesive tape is punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and stretched in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0238] The storage modulus G' (23°C) of the adhesive tape is preferably 1.0×10 4 ~1.0×10 8 Pa, more preferably 5.0×10 4 ~5.0×10 7 Pa, more preferably 1.0×10 5 ~1.0×10 7 Pa, more preferably 3.0×10 5 ~8.0×10 6 Pa. By making the breaking point stress of the adhesive tape within the range, it is easy to follow the deformation of the adherend, etc., and it is easy to obtain excellent bonding strength, and it is also possible to ensure the dimensional stability of the adhesive tape, so that suitable attachment workability can be obtained. As mentioned above, for the adhesive tape of the present invention, it is also possible to imagine that the adherend is a hard and large-area adherend such as metal or plastic. Generally speaking, the more large-area adherends are, the more difficult it is to suppress deformation during forming. If it is an adhesive tape with the above-mentioned storage modulus range, it is possible to follow the deformation of the adherend as mentioned above with the adhesive tape, and suitable bonding strength can be obtained.

[0239] The 180° peeling adhesive force of the adhesive tape is not particularly limited and can be appropriately selected according to the purpose, preferably 3N / 20mm to 50N / 20mm, more preferably 10N / 20mm to 50N / 20mm, and further preferably 15N / 20mm to 45N / 20mm. If the 180° peeling adhesive force is within the above-mentioned preferred range, it will not cause peeling or displacement from the adherend and has a moderate adhesive force, and when the adhesive tape is stretched in the horizontal direction to the vertical direction relative to the attached surface of the adherend and then peeled off, it can be easily peeled off.

[0240] The 180° peel strength of the pressure-sensitive adhesive tape refers to a value measured in accordance with JIS Z 0237.

[0241] The initial cleavage adhesive strength of the pressure-sensitive adhesive tape of the present embodiment is preferably 10 to 200 N / cm 2 , preferably 30 to 150 N / cm 2 The range of 50 to 100 N / cm is more preferred. 2 When the cleavage adhesive strength is within the above preferred range, both removability and adhesiveness can be easily achieved.

[0242] The cleavage adhesive strength of the pressure-sensitive adhesive tape is a value measured by the method described in Examples described below.

[0243] In the present embodiment, the manufacturing method of the adhesive tape is not particularly limited and can be appropriately selected from known methods. In the manufacturing method of the adhesive tape of the present embodiment, it is preferred to include an adhesive layer forming step, a substrate layer forming step and a lamination step, and further include other layer forming steps as required. In addition, it is also possible to manufacture by simultaneously performing a multi-layer simultaneous forming step of an adhesive layer forming step and a substrate layer forming step.

[0244] The adhesive layer forming step is not particularly limited as long as the adhesive layer can be formed, and can be appropriately selected according to the purpose, and examples thereof include a method of forming an adhesive layer on the surface of the release sheet by a hot press method, a casting method based on extrusion molding, a uniaxial stretching method, a sequential secondary stretching method, a simultaneous biaxial stretching method, an inflation method, a tube method, a calendaring method, a solution method, etc. Among them, a casting method based on extrusion molding and a solution method are preferred.

[0245] There are no particular restrictions on the release sheet, and it can be appropriately selected according to the purpose, for example, kraft paper, glassine paper, chemical pulp paper and other papers; resin films such as polyethylene, polypropylene (biaxially stretched polypropylene (OPP), uniaxially stretched polypropylene (CPP)), polyethylene terephthalate (PET) and the like; laminated paper formed by laminating the above paper with a resin film; a material formed by subjecting the above paper to a caulking treatment with clay, polyvinyl alcohol and the like, and then subjecting one or both sides to a release treatment with a silicone resin and the like, etc. These can be used alone or in combination of two or more.

[0246] The substrate layer formation process is just not particularly limited as long as it can form the substrate layer, and can be suitably selected according to the purpose, for example, heat pressing method, the casting method based on extrusion molding, uniaxial stretching method, successive secondary stretching method, biaxial stretching method, inflation method, tube method, calendering method, solution method etc. can be enumerated. These methods can be used alone or in combination with more than two kinds. Wherein, from the aspect that substrate layer is given suitable flexibility, stretchability, preferably the casting method based on extrusion molding, inflation method, tube method, calendering method, solution method.

[0247] In addition, in order to further improve the adhesion with the adhesive layer, the base material layer may be subjected to a surface treatment.

[0248] There are no particular restrictions on the surface treatment method, and it can be appropriately selected from known methods within the range that does not impair the properties of the adhesive tape. Examples include sandblasting, surface grinding and friction, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet irradiation treatment, oxidation treatment, and the like.

[0249] The lamination process is a process of laminating a substrate layer and an adhesive layer. There is no particular limitation on the method of laminating the substrate layer and the adhesive layer, and it can be appropriately selected from known methods, such as a method of laminating the adhesive layer and the substrate layer in a state of being attached to a release sheet formed in the adhesive layer forming process by pressurizing the adhesive layer and the substrate layer.

[0250] The adhesive tape of the present invention can be suitably used for fixing metal plates constituting relatively large electronic equipment such as thin-screen televisions, home appliances, and office automation equipment; fixing exterior parts to housings; fixing rigid parts such as exterior parts and batteries to relatively small electronic devices such as portable electronic terminals, cameras, and personal computers, etc., fixing parts in various industrial fields, temporarily fixing the parts, and labels displaying product information.

[0251] As mentioned above, although embodiment of this invention was described, the adhesive tape of this invention is not limited to the said example, It can change suitably. Example

[0252] Hereinafter, the contents of the present invention will be described in detail using examples, but the scope of the present invention is not limited to the following examples.

[0253] 1. "Measurement and evaluation of adhesive tapes" The pressure-sensitive adhesive tapes obtained in the respective Examples and Comparative Examples were measured and evaluated based on the following methods. (1) Determination of breaking stress and breaking elongation of substrate layer Each substrate layer was punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and stretched in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, thereby measuring the breaking stress and breaking elongation of the substrate layer. The results are shown in Table 1 below.

[0254] (2) Measurement of 50% modulus of substrate layer Each substrate layer was punched into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm. The substrate layer was stretched in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, thereby measuring the stress value when the substrate layer was elongated by 50%.

[0255] (3) Measurement of thickness of substrate layer and adhesive layer The substrate layer and the adhesive layer were cut at 5 locations in the width direction at intervals of 100 mm in the length direction, and the thickness was measured at 5 locations in each cut surface at intervals of 100 mm in the width direction using a TH-104 paper and film thickness measuring machine (manufactured by Tester Sangyo Co., Ltd.). The thickness of the total of 25 points was averaged as the thickness of the substrate layer and the adhesive layer.

[0256] (4) Determination of average particle size of filler The average particle size (primary particle size) of the filler was measured using a measuring machine (Microtrac) utilizing a laser diffraction scattering method.

[0257] (5) Evaluation of 180° peel adhesion The 180° peeling adhesive force was measured according to JIS Z 0237. Specifically, each adhesive tape was cut into a size of 150 mm in length and 20 mm in width, and a PET film with a thickness of 25 μm was used to line one side of the adhesive tape. Then, the other side of the adhesive tape was attached to a stainless steel plate (100 mm in length, 30 mm in width, and 3 mm in thickness) under the conditions of an atmosphere of 23°C and 50% RH, and a load of 2 kg was applied to the laminated structure of the adhesive tape and the stainless steel plate, and a roller was reciprocated and pressed once to make it pressed, and then it was left to stand for 1 hour under the conditions of an atmosphere of 23°C and 50% RH, and it was used as a test piece. Then, under the conditions of an atmosphere of 23°C and 50% RH, a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) was used to stretch the adhesive tape on the test piece in a 180° direction (horizontal direction) at a tensile speed of 300 mm / min, and the 180° peeling adhesive force of the adhesive tape was measured.

[0258] (6) Evaluation of high load holding capacity On a SUS304 steel plate of 25 mm wide × 80 mm wide specified in JIS Z0237, one side of each adhesive tape cut to 25 mm wide × 25 mm long is bonded by reciprocating pressure bonding once with a roller weighing 5 kg at a speed of 300 mm per minute at room temperature, and then placed at 23°C for 30 minutes. Then, the reverse side of the test piece is bonded to a SUS304 steel plate of 25 mm wide × 80 mm wide specified in JIS Z0237 by reciprocating pressure bonding once with a roller weighing 5 kg at a speed of 300 mm per minute at room temperature. Next, it is placed in an atmosphere of 40°C for 30 minutes. Then, a 5 kg weight is attached to the handle portion of the test piece, and the test is started by hanging it down, and the time until it falls is measured at 23°C and 50% RH. For high load holding power, a fall time of 120 minutes or more is considered qualified ( ◎ In addition, the case where the falling time is less than 120 minutes is regarded as unqualified ( × ).

[0259] (7) Evaluation of removability Regarding the re-peelability evaluation, the adhesive tape was pulled by pulling a handle provided at one end in the longitudinal direction, and the adhesive tape was stretched in a direction at 90° relative to the longitudinal direction, and the re-peelability evaluation was performed in two cases: a case where the tape was left standing for 1 minute (re-peelability 1) and a case where the tape was left standing for 30 minutes (re-peelability 2). The details are described below.

[0260] (7-1) Removability 1 (removability after leaving for 1 minute) When the 10mm wide × 60mm long adhesive tape is attached to a clean and smooth aluminum plate, the 10mm wide × 10mm long portion of the adhesive tape is attached in a state where the handle extends from the aluminum plate in order to use it as a handle. Then, the reverse side of the adhesive tape is also attached to a clean and smooth acrylic plate, and a 2kg load is applied while the roller is reciprocated and pressed once, and the plate is used as a test piece. After attachment, the adhesive tape is placed in an atmosphere of 23°C and 50% RH for 60 minutes, and the handle portion is stretched by hand at a speed of about 300mm / min in a direction of 90° relative to the length direction of the adhesive tape at 23°C and 50% RH. After peeling off 30mm, the adhesive tape is placed for 1 minute, and the handle portion is stretched by hand again in a direction of 90° at a speed of about 300mm / min. In the 10-time test, the breakage of the adhesive tape and the degree of the adhesive remaining on the adherend after the adhesive tape was peeled off were visually evaluated according to the following criteria. ◎: The adhesive tape was peeled off cleanly without any breakage or adhesive residue in 10 times. ○: The adhesive tape was peeled off without breaking in all 10 times, but adhesive residue occurred at least once. △: No breakage of the adhesive tape or adhesive residue occurred in 6 to 9 times, and the adhesive was peeled off cleanly. ×: The adhesive tape was broken or adhesive remained, or the adhesive tape could not be stretched and peeled off 5 to 10 times.

[0261] (7-2) Removability 2 (Removability after leaving for 30 minutes) When the adhesive tape with a width of 10 mm and a total length of 60 mm is attached to a clean and smooth aluminum plate, in order to use the 10 mm wide and 10 mm long portion of the adhesive tape as a handle, the handle is attached in a state where it extends from the aluminum plate. Then, the reverse side of the adhesive tape is also attached to a clean and smooth acrylic plate, and a 2 kg load is applied while reciprocating pressure is applied once with a roller to use it as a test piece. After attachment, place it in an atmosphere of 23°C and 50% RH for 60 minutes, and at 23°C and 50% RH, stretch the handle portion by hand at a speed of about 300 mm / min in a direction of 90° relative to the length direction of the adhesive tape. After peeling off 30 mm, place it for 30 minutes, and stretch the handle portion by hand again in a direction of 90° at a speed of about 300 mm / min. In the 10-time test, the breakage of the adhesive tape and the degree of the adhesive remaining on the adherend after the adhesive tape was peeled off were visually evaluated according to the following criteria. ◎: The adhesive tape was peeled off cleanly without any breakage or adhesive residue in any of the 10 times. ○: The adhesive tape was peeled off without breaking in all 10 times, but adhesive residue occurred once or more. △: No breakage of the adhesive tape or adhesive residue occurred in 6 to 9 times, and the adhesive was peeled off cleanly. ×: The adhesive tape was broken or adhesive remained, or the adhesive tape could not be stretched and peeled off 5 to 10 times.

[0262] (8) Initial cleavage adhesion (P0) The double-sided adhesive tape was cut into a size of 30 mm × 50 mm and used as a test piece. The release liner on one side of the test piece was peeled off and attached to the surface of a 3 mm thick stainless steel (SUS) plate. The release liner on the other side was peeled off and attached to the 10 mm square surface of a 10 mm × 10 mm × 40 mm long test piece. The test piece was subjected to a 50 N / cm 2 The adhesive patch was obtained by pressing for 10 seconds. Immediately after the patch was attached in an atmosphere of 23°C and 50% RH, the stainless steel sheet constituting the test piece of the patch was stretched at a rate of 1000 mm / min in an atmosphere of 23°C and 50% RH to measure the strength of the stainless steel sheet being peeled off.

[0263] (9) Splitting Adhesion Strength at 400% Elongation (P 400 ) Cut the double-sided adhesive tape into a size of 30mm×50mm and use it as a test piece. Peel off the release lining on both sides of the above test piece and make handles at both ends of the test piece. Attach a strong adhesive double-sided tape for fixing the stretched tape to the surface of a 2mm thick stainless steel plate. After stretching the test piece to 400% of its length and attaching the double-sided adhesive tape to the surface of the stainless steel plate, attach a 10mm square surface of a 10mm×10mm×40mm long test piece to the other side and apply 50N / cm 2 The adhesive patch was obtained by pressing for 10 seconds. Immediately after the patch was attached in an atmosphere of 23°C and 50% RH, the stainless steel sheet constituting the test piece of the patch was stretched at a rate of 1000 mm / min in an atmosphere of 23°C and 50% RH to measure the strength of the stainless steel sheet being peeled off.

[0264] Next, the materials and the like used in Examples and Comparative Examples are described below. 2. "Material of adhesive tape" (Base material) <Base material (1): Styrene-based base material (1)> As a substrate material used in the styrene-based substrate (1), a resin composition (1) of a styrene-ethylene butylene-styrene copolymer and a styrene-ethylene butylene copolymer is used. For the resin composition (1), a resin composition is used in which the structural unit derived from styrene represented by the chemical formula (A) is 29% by mass and the ratio of the styrene-ethylene butylene copolymer to the total amount of the resin composition is 1% by mass. The resin composition (1) was used to prepare a substrate (1) having a thickness of 50 μm by hot pressing (pressure 0.5 MPa, platen temperature 130° C., pressing time 2 minutes). The substrate (1) had a breaking stress of 78 MPa. The breaking elongation was 650%. In addition, the stress (modulus) at 50% elongation was 3 MPa.

[0265] <Base material (2): Styrene-based base material (2)> As a substrate material used in a styrene-based substrate (2), a resin composition (2) of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer is used. For the resin composition (2), a resin composition in which the structural unit derived from styrene shown in the chemical formula (A) is 26% by mass and the proportion of the styrene-isoprene copolymer relative to the total amount of the resin composition (2) is 16% by mass is used. The resin composition (2) is made into a substrate (2) with a thickness of 50 μm by hot pressing (pressure 0.5 MPa, platen temperature 130° C., pressing time 2 minutes). The breaking stress of the substrate (2) is 11 MPa. The elongation at break is 1100%. In addition, the stress (modulus) at 50% elongation is 1 MPa.

[0266] <Base material (3): PET base material (1)> As the PET substrate (1), a polyester film "Lumirror S10 50 μm" manufactured by Toray was used. This PET substrate (1) was used as the substrate (3). The breaking stress of the PET substrate (1) was 220 MPa. The breaking elongation was 180%. In addition, the stress (modulus) at 50% elongation was 130 MPa. (Adhesive composition) The adhesive composition used in the adhesive layer of the present invention contains the following filler and adhesive resin. <Packing> <<Organic Silicone Particles (1)>> As the silicone particles (1), particles having a silicone resin on the surface and a silicone rubber inside (manufactured by Shin-Etsu Chemical Co., Ltd., KMP-602, volume average particle size: 30 μm, particle size distribution (D 90 / D 10 ):5.2). <<Organic Silicone Particles (2)>> As the silicone particles (2), particles having a silicone resin on the surface and a silicone rubber inside (manufactured by Shin-Etsu Chemical Co., Ltd., KMP-600, volume average particle size: 5 μm, particle size distribution (D 90 / D 10 ):3.2). <<Acrylic Particles (1)>> As acrylic particles (1), polymethyl methacrylate particles (manufactured by Japan Exlan Industries, Ltd., FH-S010, volume average particle size: 10 μm, particle size distribution (D 90 / D 10 ):2.8).

[0267] <Binder resin> <<Synthesis of Block Copolymer>> (Synthesis example 1) In a flask with an internal volume of 1000 ml replaced with argon, 500 ml of dry toluene and 80 ml of a dry toluene solution of 0.75 g of a bis(pentamethylcyclopentadienyl)tetrahydrofuran samarium complex [(C5Me5)2SmMe(THF)] as a polymerization initiator were added to prepare a mixed solution. To the mixed solution, 12.0 ml of methyl methacrylate (MMA) was added at 0°C, and stirred at 0°C for 30 minutes. Then, 20 ml of the solution (sample 1) was sampled from the system. After the MMA was polymerized, the polymerization reaction system was cooled to -78°C, 88.0 ml of n-butyl acrylate (nBA) was added as the second monomer, and stirred at -78°C for 3 hours. Then, 20 ml of the solution (sample 2) was sampled from the system. After the nBA was polymerized, 12.0 ml of MMA was added to the polymerization system at -78°C as the third monomer, and the solution was stirred. After the solution became uniform, it was heated to 0°C and further stirred for 1 hour. 50 ml of methanol was added to the obtained reaction mixture, and the reaction was allowed to react for 2 hours at room temperature to stop the polymerization. The reaction solution after the polymerization was stopped was injected into a large amount of hexane to obtain a precipitated white precipitate. Then, a portion of the white precipitate was sampled (sample 3).

[0268] NMR measurement, DSC measurement, and GPC (gel permeation chromatography) measurement were performed on each polymer in the above samples 1 to 3. Then, based on the measurement results, the number average molecular weight (Mn), PMMA / PnBA (polymethyl methacrylate block / poly-n-butyl acrylate block) ratio, etc. were calculated, and the results confirmed that the white precipitate was a triblock copolymer of polymethyl methacrylate (PMMA) block-poly-n-butyl acrylate (PnBA) block-polymethyl methacrylate (PMMA) block (PMMA-b-PnBA-b-PMMA). In addition, it was confirmed that the syndiotacticity of the PMMA block portion of the triblock copolymer (PMMA-b-PnBA-b-PMMA, hereinafter referred to as acrylic block copolymer (1)) was 71%, the glass transition temperature of the block portion was 113.7°C, the glass transition temperature of the PnBA block portion was -46.8°C, the Mn of the copolymer as a whole was 95936, the Mw / Mn (molecular weight distribution) of the copolymer as a whole was 1.09, and the ratio of each polymer block was PMMA (11 mass %)-PnBA (78 mass %)-PMMA (11 mass %).

[0269] (Synthesis example 2) In a flask with an internal volume of 1000 ml replaced with argon, 500 ml of dry toluene and 80 ml of a dry toluene solution of 0.75 g of a bis(pentamethylcyclopentadienyl)tetrahydrofuran samarium complex [(C5Me5)2SmMe(THF)] as a polymerization initiator were added to prepare a mixed solution. To the mixed solution, 6.0 ml of methyl methacrylate (MMA) was added at 0°C, and stirred at 0°C for 30 minutes. Then, 20 ml of the solution was sampled from the system (sample 4). After the MMA was polymerized, the polymerization reaction system was cooled to -78°C, 27.2 ml of n-butyl acrylate (nBA) and 22.1 ml of 2-ethylhexyl acrylate (2EHA) were added as the second monomer, and stirred at -78°C for 3 hours. 20 ml of the solution was sampled from the system (sample 5). After the nBA was polymerized, 6.0 ml of MMA was added to the polymerization system at -78°C as the third monomer, and the solution was stirred. After the solution becomes uniform, it is heated to 0°C and stirred for another hour. 50 ml of methanol is added to the obtained reaction mixture, and the reaction is carried out at room temperature for 2 hours to stop the polymerization. The reaction solution after the polymerization is stopped is injected into a large amount of hexane to obtain a white precipitate. Then, a portion of the white precipitate is sampled (sample 6).

[0270] NMR measurement, DSC measurement, and GPC (gel permeation chromatography) measurement were performed on each polymer in the samples 4 to 6. Then, based on the measurement results, the number average molecular weight (Mn), PMMA / PnBA / P2EHA (polymethyl methacrylate / poly-n-butyl acrylate / poly-2-ethylhexyl acrylate) ratio, etc. were calculated, and the white precipitate was confirmed to be a triblock copolymer of polymethyl methacrylate (PMMA) block-poly-n-butyl acrylate (PnBA) / poly-2-ethylhexyl acrylate (2EHA) block-polymethyl methacrylate (PMMA) block (PMMA-b-PnBA / 2EHA-b-PMMA). Furthermore, it was confirmed that the syndiotacticity of the PMMA block portion of the triblock copolymer (PMMA-b-PnBA / 2EHA-b-PMMA, hereinafter referred to as acrylic block copolymer (2)) was 75%, the glass transition temperature of the block portion was 105.8°C, the glass transition temperature of the PnBA block portion was -53.6°C, the Mn of the copolymer as a whole was 51370, the Mw / Mn (molecular weight distribution) of the copolymer as a whole was 1.15, and the ratio of each polymer block was PMMA (10 mass %)-PnBA (44 mass %) / 2EHA (36 mass %)-PMMA (10 mass %).

[0271] ~<<Other Binder Resins>> (Synthesis example 3) As the binder resin, an acrylic random copolymer (1) obtained by the following synthesis was used. 97.97 parts by mass of n-butyl acrylate, 2 parts by mass of acrylic acid, and 0.03 parts by mass of 4-hydroxybutyl acrylate were supplied to ethyl acetate containing 0.2 parts by mass of azobisisobutyronitrile as a polymerization initiator, and solution polymerization was performed at 77° C. for 8 hours to obtain an acrylic random copolymer (1). Mw was 700,000, and Mw / Mn (molecular weight distribution) was 4.7. (SIS Rubber) As the binder resin, SIS rubber (styrene triblock copolymer) (Quintac 3270 manufactured by Zeon, styrene content 24%, SI diblock content 67%) was used. The Mw of the styrene triblock copolymer was 175,000, and the Mw / Mn (molecular weight distribution) was 1.05. The Mw of the diblock copolymer was 84,000, and the Mw / Mn (molecular weight distribution) was 1.05.

[0272] <Preparation of Adhesive Resin Composition> Adhesive composition (1) 50 parts by mass of a terpene phenol tackifier resin (Tamanol T-803L, Arakawa Chemical Industries, Ltd., softening point 150° C.) was mixed and stirred with 100 parts by mass of the acrylic block copolymer (1) obtained in Synthesis Example 1, and then ethyl acetate was added to obtain a binder resin solution (1) having a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the binder resin solution (1), and the mixture was stirred and mixed to obtain a uniform binder composition (1) having a solid content of 40% by mass.

[0273] Adhesive composition (2) 50 parts by mass of a terpene phenol tackifier resin (YS Polyster T130, Yasuhara Chemical Co., Ltd., softening point 130° C.) was mixed and stirred with 100 parts by mass of the acrylic block copolymer (1) obtained in Synthesis Example 1, and then ethyl acetate was added to obtain a binder resin solution (2) having a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the binder resin solution (2), and the mixture was stirred and mixed to obtain a uniform binder composition (2) having a solid content of 40% by mass.

[0274] Adhesive composition (3) 50 parts by mass of a terpene phenol tackifier resin (YS Polyster T130, Yasuhara Chemical Co., Ltd., softening point 130° C.) was mixed and stirred with 100 parts by mass of the acrylic block copolymer (1) obtained in Synthesis Example 1, and then ethyl acetate was added to obtain a binder resin solution (3) having a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (2) and ethyl acetate were added to 100 parts by mass of the solid content of the binder resin solution (3), and the mixture was stirred and mixed to obtain a uniform binder composition (3) having a solid content of 40% by mass.

[0275] Adhesive composition (4) 50 parts by mass of a terpene phenol tackifier resin (YS Polyster T130, Yasuhara Chemical Co., Ltd., softening point 130° C.) was mixed and stirred with 100 parts by mass of the acrylic block copolymer (2) obtained in Synthesis Example 2, and then ethyl acetate was added to obtain a binder resin solution (4) having a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the binder resin solution (4), and the mixture was stirred and mixed to obtain a uniform binder composition (4) having a solid content of 40% by mass.

[0276] Adhesive composition (5) 50 parts by mass of a terpene phenol tackifier resin (YS Polyster T130, Yasuhara Chemical Co., Ltd., softening point 130° C.) was mixed and stirred with 100 parts by mass of the acrylic block copolymer (1) obtained in Synthesis Example 1, and then ethyl acetate was added to obtain a binder resin solution (5) having a solid content of 35% by mass. Next, 38 parts by mass of acrylic particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the binder resin solution (5), and the mixture was stirred and mixed to obtain a uniform binder composition (5) having a solid content of 40% by mass.

[0277] Adhesive composition (6) 50 parts by mass of a terpene phenol tackifier resin (YS Polyster T130, Yasuhara Chemical Co., Ltd., softening point 130° C.) was mixed and stirred with 100 parts by mass of the acrylic block copolymer (1) obtained in Synthesis Example 1, and then ethyl acetate was added to obtain a binder resin solution (6) having a solid content of 35% by mass. Next, 70 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the binder resin solution (4), and the mixture was stirred and mixed to obtain a uniform binder composition (6) having a solid content of 40% by mass.

[0278] Adhesive composition (7) 50 parts by mass of a rosin-based tackifier resin (Super Ester A-100, Arakawa Chemical Co., Ltd., softening point 100° C.) was mixed and stirred with 100 parts by mass of a styrene-based triblock copolymer (Quintac 3270 manufactured by Zeon Co., Ltd., styrene content 24%, SI diblock content 67%) as a binder resin, and toluene was added to obtain a binder resin solution (7) having a solid content of 35% by mass. 38 parts by mass of silicone particles (1) and toluene were added to 100 parts by mass of the solid content of the binder resin solution (7), and the mixture was stirred and mixed to make it uniform, thereby obtaining a binder composition (7) having a solid content of 40% by mass.

[0279] Adhesive composition (8) 100 parts by mass of the acrylic random copolymer obtained in Synthesis Example 3 was mixed with 5 parts by mass of a rosin-based tackifier resin (Haritac PCJ, Harima Chemicals Co., Ltd., softening point 135°C) and 45 parts by mass of a petroleum-based tackifier resin (FTR6125, Mitsui Chemicals, Inc., softening point 125°C) and stirred, and then ethyl acetate was added to obtain a binder resin solution (8) having a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the binder resin solution (8), and the mixture was stirred and mixed to obtain a uniform binder composition (8) having a solid content of 40% by mass.

[0280] 3. "Manufacture of adhesive tape" [Example 1] The adhesive composition (1) was applied to a release liner (FilmBina 75E-0010GT, manufactured by Fujimori Industries, Ltd., hereinafter the same) using an applicator so that the thickness after drying was 50 μm, and dried at 80° C. for 3 minutes to prepare an adhesive layer. Next, both surfaces of the substrate (1) as a substrate layer were subjected to corona treatment so that the wetting tension reached 52 mN / m, and then the adhesive layer was attached to both surfaces, and the laminated structure of the substrate layer and the adhesive layer was pressed at 0.2 MPa to laminate, thereby preparing an adhesive tape of Example 1. The adhesive tape obtained by the above method was evaluated, and the results are shown in Table 1.

[0281] [Example 2] The adhesive tape of Example 2 was produced in the same manner as in Example 1 except that the adhesive composition (1) was changed to the adhesive composition (2). The obtained adhesive tapes were evaluated by the above method. The results are shown in Table 1.

[0282] [Example 3] The pressure-sensitive adhesive tape of Example 3 was produced in the same manner as in Example 1 except that the pressure-sensitive adhesive composition (1) was changed to the pressure-sensitive adhesive composition (3). The pressure-sensitive adhesive tapes obtained by the above-mentioned methods were evaluated. The results are shown in Table 1.

[0283] [Example 4] The pressure-sensitive adhesive tape of Example 4 was produced in the same manner as in Example 1 except that the pressure-sensitive adhesive composition (1) was changed to the pressure-sensitive adhesive composition (4). The pressure-sensitive adhesive tapes obtained were evaluated by the above-mentioned methods. The results are shown in Table 1.

[0284] [Example 5] The pressure-sensitive adhesive tape of Example 5 was produced in the same manner as in Example 1 except that the pressure-sensitive adhesive composition (1) was changed to the pressure-sensitive adhesive composition (5). The pressure-sensitive adhesive tapes obtained were evaluated by the above-mentioned methods. The results are shown in Table 1.

[0285] [Example 6] The pressure-sensitive adhesive tape of Example 6 was produced in the same manner as in Example 1 except that the pressure-sensitive adhesive composition (1) was changed to the pressure-sensitive adhesive composition (6). The pressure-sensitive adhesive tapes obtained were evaluated by the above-mentioned methods. The results are shown in Table 1.

[0286] [Example 7] The pressure-sensitive adhesive tape of Example 7 was produced in the same manner as in Example 1 except that the pressure-sensitive adhesive composition (1) was changed to the pressure-sensitive adhesive composition (7). The pressure-sensitive adhesive tapes obtained were evaluated by the above-mentioned methods. The results are shown in Table 1.

[0287] [Example 8] The pressure-sensitive adhesive tape of Example 8 was produced in the same manner as in Example 1 except that the pressure-sensitive adhesive substrate (1) was changed to substrate (2). The pressure-sensitive adhesive tape obtained by the above-mentioned method was evaluated. The results are shown in Table 1.

[0288] [Comparative Example 1] A pressure-sensitive adhesive tape of Comparative Example 1 was produced in the same manner as in Example 1 except that the pressure-sensitive adhesive composition (1) was changed to the pressure-sensitive adhesive composition (8). The pressure-sensitive adhesive tape obtained was evaluated in the same manner as described above. The results are shown in Table 2.

[0289] [Comparative Example 2] The adhesive tape of Comparative Example 2 was produced in the same manner as in Example 1 except that the substrate (1) was changed to the substrate (3). The obtained adhesive tapes were evaluated by the above method, and the results are shown in Table 2. It should be noted that in Comparative Example 2, the PET substrate broke before the elongation reached 400%, so the P value could not be calculated. 400 The value of .

[0290] [Table 1]

[0291] [Table 2]

Claims

1. An adhesive tape comprising a substrate layer and an adhesive layer, The substrate layer has a breaking stress of 1 to 100 MPa and a breaking elongation of 400 to 3000%. The adhesive tape satisfies the following relationship (i): P 400 / P0≤0.9 (i) In the above relational formula (i), P0 represents the initial cleavage adhesion of the adhesive tape, and P 400 It represents the cleavage adhesion when the adhesive tape is stretched 400%, where P0 and P 400 The unit is N / cm 2 , The initial splitting adhesive force P0 is 0.1-200 N / cm 2 , The adhesive force P when stretched 400% 400 0.001~70N / cm 2 .

2. The adhesive tape according to claim 1, wherein The adhesive layer includes a styrenic block copolymer.

3. The adhesive tape according to claim 2, wherein The pressure-sensitive adhesive tape contains 30 to 100% by mass of the styrene-based block copolymer based on the entire binder resin.

4. The adhesive tape according to claim 1, wherein The adhesive layer comprises a triblock copolymer having repeating units represented by the general formula (1): In the above general formula (1), A, B and C each independently represent a repeating unit, A and C each independently represent an alkyl methacrylate monomer unit, B represents an alkyl acrylate monomer unit, p, q and r each independently represent the degree of polymerization of each monomer unit, A and C are the same, or are alkyl methacrylate monomer units with different chemical structures, In the above general formula (1), * represents a bonding position with other atoms.

5. The adhesive tape according to claim 4, wherein The pressure-sensitive adhesive tape contains 30 to 100% by mass of the triblock copolymer based on the entire binder resin.

6. The adhesive tape according to claim 4, wherein In the general formula (1), "-(A) p The syndiotacticity of the polymer block in the -" part shows a ratio of rr triads of more than 65%, In the general formula (1), "-(C) r The syndiotacticity of the polymer block in the "-" portion showed a ratio of rr triads of 65% or more.

7. The adhesive tape according to claim 1 or 2, wherein The storage modulus G' of the adhesive layer at 23°C is 1.0×10 5 ~1.0×10 7 Pa.

8. The adhesive tape according to claim 1 or 2, wherein The adhesive layer contains a filler.

9. The adhesive tape according to claim 8, wherein The filler is an organic filler.

10. The adhesive tape according to claim 9, wherein The organic filler is a silicon-based resin.

Citation Information

Patent Citations

  • Thermosetting epoxy resin composition

    JP1984096122A

  • Production of silicone powder

    JP1987270660A

  • Production of particulate silicone rubber

    JP1988077942A

  • Production of fine powder of silicone elastomer

    JP1991093834A

  • Production of fine powder of silicone elastomer

    JP1992198324A